Nondeterminism in the presence of a diverse or unknown future - Boker, Udi; Kuperberg, Denis; Kupferman, Orna; Skrzypczak, Michał
Choices made by nondeterministic word automata depend on both the past (the prefix of the word read so far) and the future (the suffix yet to be read). In several applications, most notably synthesis, the future is diverse or unknown, leading to algorithms that are based on deterministic automata. Hoping to retain some of the advantages of nondeterministic automata, researchers have studied restricted classes of nondeterministic automata. Three such classes are nondeterministic automata that are good for trees (GFT; i.e., ones that can be expanded to tree automata accepting the derived tree languages, thus whose choices should satisfy diverse futures), good for games (GFG; i.e., ones whose choices depend only on the past), and determinizable by pruning (DBP; i.e., ones that embody equivalent deterministic automata). The theoretical properties and relative merits of the different classes are still open, having vagueness on whether they really differ from deterministic automata. In particular, while DBP ⊆ GFG ⊆ GFT, it is not known whether every GFT automaton is GFG and whether every GFG automaton is DBP. Also open is the possible succinctness of GFG and GFT automata compared to deterministic automata. We study these problems for ω-regular automata with all common acceptance conditions. We show that GFT=GFG⊃DBP, and describe a determinization construction for GFG automata.

Geometry of the faithfulness assumption in causal inference - Uhler, Caroline; Raskutti, Garvesh; Bühlmann, Peter; Yu, Bin (The Annals of Statistics)
Many algorithms for inferring causality rely heavily on the faithfulness assumption. The main justification for imposing this assumption is that the set of unfaithful distributions has Lebesgue measure zero, since it can be seen as a collection of hypersurfaces in a hypercube. However, due to sampling error the faithfulness condition alone is not sufficient for statistical estimation, and strong-faithfulness has been proposed and assumed to achieve uniform or high-dimensional consistency. In contrast to the plain faithfulness assumption, the set of distributions that is not strong-faithful has nonzero Lebesgue measure and in fact, can be surprisingly large as we show in this paper. We study the strong-faithfulness condition from a geometric and combinatorial point of view and give upper and lower bounds on the Lebesgue measure of strong-faithful distributions for various classes of directed acyclic graphs. Our results imply fundamental limitations for the PC-algorithm and potentially also for other algorithms based on partial correlation testing in the Gaussian case.

Privacy-preserving data sharing for genome-wide association studies - Uhler, Caroline; Slavkovic, Aleksandra; Fienberg, Stephen (Journal of Privacy and Confidentiality)
Traditional statistical methods for confidentiality protection of statistical databases do not scale well to deal with GWAS databases especially in terms of guarantees regarding protection from linkage to external information. The more recent concept of differential privacy, introduced by the cryptographic community, is an approach which provides a rigorous definition of privacy with meaningful privacy guarantees in the presence of arbitrary external information, although the guarantees may come at a serious price in terms of data utility. Building on such notions, we propose new methods to release aggregate GWAS data without compromising an individual’s privacy. We present methods for releasing differentially private minor allele frequencies, chi-square statistics and p-values. We compare these approaches on simulated data and on a GWAS study of canine hair length involving 685 dogs. We also propose a privacy-preserving method for finding genome-wide associations based on a differentially-private approach to penalized logistic regression.

Quantitative relaxation of concurrent data structures - Henzinger, Thomas A; Kirsch, Christoph; Payer, Hannes; Sezgin, Ali; Sokolova, Ana (Proceedings of the 40th annual ACM SIGPLAN-SIGACT symposium on Principles of programming language)
There is a trade-off between performance and correctness in implementing concurrent data structures. Better performance may be achieved at the expense of relaxing correctness, by redefining the semantics of data structures. We address such a redefinition of data structure semantics and present a systematic and formal framework for obtaining new data structures by quantitatively relaxing existing ones. We view a data structure as a sequential specification S containing all "legal" sequences over an alphabet of method calls. Relaxing the data structure corresponds to defining a distance from any sequence over the alphabet to the sequential specification: the k-relaxed sequential specification contains all sequences over the alphabet within distance k from the original specification. In contrast to other existing work, our relaxations are semantic (distance in terms of data structure states). As an instantiation of our framework, we present two simple yet generic relaxation schemes, called out-of-order and stuttering relaxation, along with several ways of computing distances. We show that the out-of-order relaxation, when further instantiated to stacks, queues, and priority queues, amounts to tolerating bounded out-of-order behavior, which cannot be captured by a purely syntactic relaxation (distance in terms of sequence manipulation, e.g. edit distance). We give concurrent implementations of relaxed data structures and demonstrate that bounded relaxations provide the means for trading correctness for performance in a controlled way. The relaxations are monotonic which further highlights the trade-off: increasing k increases the number of permitted sequences, which as we demonstrate can lead to better performance. Finally, since a relaxed stack or queue also implements a pool, we actually have new concurrent pool implementations that outperform the state-of-the-art ones.

Quantitative abstraction refinement - Cerny, Pavol; Henzinger, Thomas A; Radhakrishna, Arjun (Proceedings of the 40th annual ACM SIGPLAN-SIGACT symposium on Principles of programming language)
We propose a general framework for abstraction with respect to quantitative properties, such as worst-case execution time, or power consumption. Our framework provides a systematic way for counter-example guided abstraction refinement for quantitative properties. The salient aspect of the framework is that it allows anytime verification, that is, verification algorithms that can be stopped at any time (for example, due to exhaustion of memory), and report approximations that improve monotonically when the algorithms are given more time. We instantiate the framework with a number of quantitative abstractions and refinement schemes, which differ in terms of how much quantitative information they keep from the original system. We introduce both state-based and trace-based quantitative abstractions, and we describe conditions that define classes of quantitative properties for which the abstractions provide over-approximations. We give algorithms for evaluating the quantitative properties on the abstract systems. We present algorithms for counter-example based refinements for quantitative properties for both state-based and segment-based abstractions. We perform a case study on worst-case execution time of executables to evaluate the anytime verification aspect and the quantitative abstractions we proposed.

Recognizing straight skeletons and Voronoi diagrams and reconstructing their input - Biedl, Therese; Held, Martin; Huber, Stefan
A straight skeleton is a well-known geometric structure, and several algorithms exist to construct the straight skeleton for a given polygon or planar straight-line graph. In this paper, we ask the reverse question: Given the straight skeleton (in form of a planar straight-line graph, with some rays to infinity), can we reconstruct a planar straight-line graph for which this was the straight skeleton? We show how to reduce this problem to the problem of finding a line that intersects a set of convex polygons. We can find these convex polygons and all such lines in $O(nlog n)$ time in the Real RAM computer model, where $n$ denotes the number of edges of the input graph. We also explain how our approach can be used for recognizing Voronoi diagrams of points, thereby completing a partial solution provided by Ash and Bolker in 1985.

Reconstructing polygons from embedded straight skeletons - Biedl, Therese; Held, Martin; Huber, Stefan (29th European Workshop on Computational Geometry)
A straight skeleton is a well-known geometric structure, and several algorithms exist to construct the straight skeleton for a given polygon. In this paper, we ask the reverse question: Given the straight skeleton (in form of a tree with a drawing in the plane, but with the exact position of the leaves unspecified), can we reconstruct the polygon? We show that in most cases there exists at most one polygon; in the remaining case there is an infinite number of polygons determined by one angle that can range in an interval. We can find this (set of) polygon(s) in linear time in the Real RAM computer model.

Tree interpolation in Vampire - Blanc, Régis; Gupta, Ashutosh; Kovács, Laura; Kragl, Bernhard
We describe new extensions of the Vampire theorem prover for computing tree interpolants. These extensions generalize Craig interpolation in Vampire, and can also be used to derive sequence interpolants. We evaluated our implementation on a large number of examples over the theory of linear integer arithmetic and integer-indexed arrays, with and without quantifiers. When compared to other methods, our experiments show that some examples could only be solved by our implementation.

Multi-objective discounted reward verification in graphs and MDPs - Chatterjee, Krishnendu; Forejt, Vojtěch; Wojtczak, Dominik
We study the problem of achieving a given value in Markov decision processes (MDPs) with several independent discounted reward objectives. We consider a generalised version of discounted reward objectives, in which the amount of discounting depends on the states visited and on the objective. This definition extends the usual definition of discounted reward, and allows to capture the systems in which the value of different commodities diminish at different and variable rates. We establish results for two prominent subclasses of the problem, namely state-discount models where the discount factors are only dependent on the state of the MDP (and independent of the objective), and reward-discount models where they are only dependent on the objective (but not on the state of the MDP). For the state-discount models we use a straightforward reduction to expected total reward and show that the problem whether a value is achievable can be solved in polynomial time. For the reward-discount model we show that memory and randomisation of the strategies are required, but nevertheless that the problem is decidable and it is sufficient to consider strategies which after a certain number of steps behave in a memoryless way. For the general case, we show that when restricted to graphs (i.e. MDPs with no randomisation), pure strategies and discount factors of the form 1/n where n is an integer, the problem is in PSPACE and finite memory suffices for achieving a given value. We also show that when the discount factors are not of the form 1/n, the memory required by a strategy can be infinite.

Elementary modal logics over transitive structures - Michaliszyn, Jakub; Otop, Jan
We show that modal logic over universally first-order definable classes of transitive frames is decidable. More precisely, let K be an arbitrary class of transitive Kripke frames definable by a universal first-order sentence. We show that the global and finite global satisfiability problems of modal logic over K are decidable in NP, regardless of choice of K. We also show that the local satisfiability and the finite local satisfiability problems of modal logic over K are decidable in NEXPTIME.

Untangling two systems of noncrossing curves - Matoušek, Jiří; Sedgwick, Eric; Tancer, Martin; Wagner, Uli
We consider two systems (α1,...,αm) and (β1,...,βn) of curves drawn on a compact two-dimensional surface ℳ with boundary. Each αi and each βj is either an arc meeting the boundary of ℳ at its two endpoints, or a closed curve. The αi are pairwise disjoint except for possibly sharing endpoints, and similarly for the βj. We want to "untangle" the βj from the αi by a self-homeomorphism of ℳ; more precisely, we seek an homeomorphism φ: ℳ → ℳ fixing the boundary of ℳ pointwise such that the total number of crossings of the αi with the φ(βj) is as small as possible. This problem is motivated by an application in the algorithmic theory of embeddings and 3-manifolds. We prove that if ℳ is planar, i.e., a sphere with h ≥ 0 boundary components ("holes"), then O(mn) crossings can be achieved (independently of h), which is asymptotically tight, as an easy lower bound shows. In general, for an arbitrary (orientable or nonorientable) surface ℳ with h holes and of (orientable or nonorientable) genus g ≥ 0, we obtain an O((m + n)4) upper bound, again independent of h and g.

Learning with rounding, revisited: New reduction properties and applications - Alwen, Joel F; Krenn, Stephan; Pietrzak, Krzysztof Z; Wichs, Daniel
The learning with rounding (LWR) problem, introduced by Banerjee, Peikert and Rosen at EUROCRYPT ’12, is a variant of learning with errors (LWE), where one replaces random errors with deterministic rounding. The LWR problem was shown to be as hard as LWE for a setting of parameters where the modulus and modulus-to-error ratio are super-polynomial. In this work we resolve the main open problem and give a new reduction that works for a larger range of parameters, allowing for a polynomial modulus and modulus-to-error ratio. In particular, a smaller modulus gives us greater efficiency, and a smaller modulus-to-error ratio gives us greater security, which now follows from the worst-case hardness of GapSVP with polynomial (rather than super-polynomial) approximation factors. As a tool in the reduction, we show that there is a “lossy mode” for the LWR problem, in which LWR samples only reveal partial information about the secret. This property gives us several interesting new applications, including a proof that LWR remains secure with weakly random secrets of sufficient min-entropy, and very simple constructions of deterministic encryption, lossy trapdoor functions and reusable extractors. Our approach is inspired by a technique of Goldwasser et al. from ICS ’10, which implicitly showed the existence of a “lossy mode” for LWE. By refining this technique, we also improve on the parameters of that work to only requiring a polynomial (instead of super-polynomial) modulus and modulus-to-error ratio.

Digital signatures with minimal overhead from indifferentiable random invertible functions - Kiltz, Eike; Pietrzak, Krzysztof Z; Szegedy, Mario
In a digital signature scheme with message recovery, rather than transmitting the message m and its signature σ, a single enhanced signature τ is transmitted. The verifier is able to recover m from τ and at the same time verify its authenticity. The two most important parameters of such a scheme are its security and overhead |τ| − |m|. A simple argument shows that for any scheme with “n bits security” |τ| − |m| ≥ n, i.e., the overhead is lower bounded by the security parameter n. Currently, the best known constructions in the random oracle model are far from this lower bound requiring an overhead of n + logq h , where q h is the number of queries to the random oracle. In this paper we give a construction which basically matches the n bit lower bound. We propose a simple digital signature scheme with n + o(logq h ) bits overhead, where q h denotes the number of random oracle queries. Our construction works in two steps. First, we propose a signature scheme with message recovery having optimal overhead in a new ideal model, the random invertible function model. Second, we show that a four-round Feistel network with random oracles as round functions is tightly “public-indifferentiable” from a random invertible function. At the core of our indifferentiability proof is an almost tight upper bound for the expected number of edges of the densest “small” subgraph of a random Cayley graph, which may be of independent interest.

Linked (Open) Data - Bibliographische Daten im Semantic Web - Danowski, Patrick; Goldfarb, Doron; Schaffner, Verena; Seidler, Wolfram (VÖB Mitteilungen)
Linked (Open) Data - bibliographic data on the Semantic Web. Report of the Working Group on Linked Data to the plenary assembly of the Austrian Library Network (translation of the title). Linked Data stands for a certain approach to publishing data on the Web. The underlying idea is to harmonise heterogeneous data sources of different origin in order to improve their accessibility and interoperability, effectively making them queryable as a big distributed database. This report summarises relevant developments in Europe as well as the Linked Data Working Group‘s strategic and technical considerations regarding the publishing of the Austrian Library Network’s (OBV’s) bibliographic datasets. It concludes with the mutual agreement that the implementation of Linked Data principles within the OBV can only be taken into consideration accompanied by a discussion about the provision of the datasets under a free license.

Efficient signatures of knowledge and DAA in the standard model - Bernhard, David; Fuchsbauer, Georg; Ghadafi, Essam
Direct Anonymous Attestation (DAA) is one of the most complex cryptographic protocols deployed in practice. It allows an embedded secure processor known as a Trusted Platform Module (TPM) to attest to the configuration of its host computer without violating the owner’s privacy. DAA has been standardized by the Trusted Computing Group and ISO/IEC. The security of the DAA standard and all existing schemes is analyzed in the random-oracle model. We provide the first constructions of DAA in the standard model, that is, without relying on random oracles. Our constructions use new building blocks, including the first efficient signatures of knowledge in the standard model, which have many applications beyond DAA.

Neural development is dependent on the function of specificity protein 2 in cell cycle progression - Liang, Huixuan; Xiao, Guanxi; Yin, Haifeng; Hippenmeyer, Simon; Horowitz, Jonathan; Ghashghaei, Troy (Development)
Faithful progression through the cell cycle is crucial to the maintenance and developmental potential of stem cells. Here, we demonstrate that neural stem cells (NSCs) and intermediate neural progenitor cells (NPCs) employ a zinc-finger transcription factor specificity protein 2 (Sp2) as a cell cycle regulator in two temporally and spatially distinct progenitor domains. Differential conditional deletion of Sp2 in early embryonic cerebral cortical progenitors, and perinatal olfactory bulb progenitors disrupted transitions through G1, G2 and M phases, whereas DNA synthesis appeared intact. Cell-autonomous function of Sp2 was identified by deletion of Sp2 using mosaic analysis with double markers, which clearly established that conditional Sp2-null NSCs and NPCs are M phase arrested in vivo. Importantly, conditional deletion of Sp2 led to a decline in the generation of NPCs and neurons in the developing and postnatal brains. Our findings implicate Sp2-dependent mechanisms as novel regulators of cell cycle progression, the absence of which disrupts neurogenesis in the embryonic and postnatal brain.

Optimal Coalition Structures in Cooperative Graph Games - Bachrach, Yoram; Kohli, Pushmeet; Kolmogorov, Vladimir; Zadimoghaddam, Morteza
Representation languages for coalitional games are a key research area in algorithmic game theory. There is an inher- ent tradeoff between how general a language is, allowing it to capture more elaborate games, and how hard it is computationally to optimize and solve such games. One prominent such language is the simple yet expressive Weighted Graph Games (WGGs) representation (Deng and Papadimitriou 1994), which maintains knowledge about synergies between agents in the form of an edge weighted graph. We consider the problem of finding the optimal coalition structure in WGGs. The agents in such games are vertices in a graph, and the value of a coalition is the sum of the weights of the edges present between coalition members. The optimal coalition structure is a partition of the agents to coalitions, that maximizes the sum of utilities obtained by the coalitions. We show that finding the optimal coalition structure is not only hard for general graphs, but is also intractable for restricted families such as planar graphs which are amenable for many other combinatorial problems. We then provide algorithms with constant factor approximations for planar, minorfree and bounded degree graphs.

Reweighted message passing revisited - Vladimir Kolmogorov
We propose a new family of message passing techniques for MAP estimation in graphical models which we call Sequential Reweighted Message Passing (SRMP). Special cases include well-known techniques such as Min-Sum Diusion (MSD) and a faster Sequential Tree-Reweighted Message Passing (TRW-S). Importantly, our derivation is simpler than the original derivation of TRW-S, and does not involve a decomposition into trees. This allows easy generalizations. We present such a generalization for the case of higher-order graphical models, and test it on several real-world problems with promising results.

A serrate-notch-canoe complex mediates essential interactions between glia and neuroepithelial cells during Drosophila optic lobe development - Pérez Gómez, Raquel; Slovakova, Jana; Rives Quinto, Noemí; Krejčí, Alena; Carmena, Ana (Journal of Cell Science)
It is firmly established that interactions between neurons and glia are fundamental across species for the correct establishment of a functional brain. Here, we found that the glia of the Drosophila larval brain display an essential non-autonomous role during the development of the optic lobe. The optic lobe develops from neuroepithelial cells that proliferate by dividing symmetrically until they switch to asymmetric/differentiative divisions that generate neuroblasts. The proneural gene lethal of scute (l9sc) is transiently activated by the epidermal growth factor receptor (EGFR)-Ras signal transduction pathway at the leading edge of a proneural wave that sweeps from medial to lateral neuroepithelium, promoting this switch. This process is tightly regulated by the tissue-autonomous function within the neuroepithelium of multiple signaling pathways, including EGFR-Ras and Notch. This study shows that the Notch ligand Serrate (Ser) is expressed in the glia and it forms a complex in vivo with Notch and Canoe, which colocalize at the adherens junctions of neuroepithelial cells. This complex is crucial for interactions between glia and neuroepithelial cells during optic lobe development. Ser is tissue-autonomously required in the glia where it activates Notch to regulate its proliferation, and non-autonomously in the neuroepithelium where Ser induces Notch signaling to avoid the premature activation of the EGFR-Ras pathway and hence of L9sc. Interestingly, different Notch activity reporters showed very different expression patterns in the glia and in the neuroepithelium, suggesting the existence of tissue-specific factors that promote the expression of particular Notch target genes or/and a reporter response dependent on different thresholds of Notch signaling.

Potts model, parametric maxflow and k-submodular functions - Gridchyn, Igor; Kolmogorov, Vladimir
The problem of minimizing the Potts energy function frequently occurs in computer vision applications. One way to tackle this NP-hard problem was proposed by Kovtun [19, 20]. It identifies a part of an optimal solution by running k maxflow computations, where k is the number of labels. The number of “labeled” pixels can be significant in some applications, e.g. 50-93% in our tests for stereo. We show how to reduce the runtime to O (log k) maxflow computations (or one parametric maxflow computation). Furthermore, the output of our algorithm allows to speed-up the subsequent alpha expansion for the unlabeled part, or can be used as it is for time-critical applications. To derive our technique, we generalize the algorithm of Felzenszwalb et al. [7] for Tree Metrics . We also show a connection to k-submodular functions from combinatorial optimization, and discuss k-submodular relaxations for general energy functions.

Packing ellipsoids with overlap - Uhler, Caroline; Wright, Stephen (SIAM Review)
The problem of packing ellipsoids of different sizes and shapes into an ellipsoidal container so as to minimize a measure of overlap between ellipsoids is considered. A bilevel optimization formulation is given, together with an algorithm for the general case and a simpler algorithm for the special case in which all ellipsoids are in fact spheres. Convergence results are proved and computational experience is described and illustrated. The motivating application-chromosome organization in the human cell nucleus-is discussed briefly, and some illustrative results are presented.

The influence of demography and local mating environment on sex ratios in a wind-pollinated dioecious plant - Pickup, Melinda; Barrett, Spencer (Ecology and Evolution)
Negative frequency-dependent selection should result in equal sex ratios in large populations of dioecious flowering plants, but deviations from equality are commonly reported. A variety of ecological and genetic factors can explain biased sex ratios, although the mechanisms involved are not well understood. Most dioecious species are long-lived and/or clonal complicating efforts to identify stages during the life cycle when biases develop. We investigated the demographic correlates of sex-ratio variation in two chromosome races of Rumex hastatulus, an annual, wind-pollinated colonizer of open habitats from the southern USA. We examined sex ratios in 46 populations and evaluated the hypothesis that the proximity of males in the local mating environment, through its influence on gametophytic selection, is the primary cause of female-biased sex ratios. Female-biased sex ratios characterized most populations of R. hastatulus (mean sex ratio = 0.62), with significant female bias in 89% of populations. Large, high-density populations had the highest proportion of females, whereas smaller, low-density populations had sex ratios closer to equality. Progeny sex ratios were more female biased when males were in closer proximity to females, a result consistent with the gametophytic selection hypothesis. Our results suggest that interactions between demographic and genetic factors are probably the main cause of female-biased sex ratios in R. hastatulus. The annual life cycle of this species may limit the scope for selection against males and may account for the weaker degree of bias in comparison with perennial Rumex species.

Tension-oriented cell divisions limit anisotropic tissue tension in epithelial spreading during zebrafish epiboly - Campinho, Pedro; Behrndt, Martin; Ranft, Jonas; Risler, Thomas; Minc, Nicolas; Heisenberg, Carl-Philipp J (Nature Cell Biology)
Epithelial spreading is a common and fundamental aspect of various developmental and disease-related processes such as epithelial closure and wound healing. A key challenge for epithelial tissues undergoing spreading is to increase their surface area without disrupting epithelial integrity. Here we show that orienting cell divisions by tension constitutes an efficient mechanism by which the enveloping cell layer (EVL) releases anisotropic tension while undergoing spreading during zebrafish epiboly. The control of EVL cell-division orientation by tension involves cell elongation and requires myosin II activity to align the mitotic spindle with the main tension axis. We also found that in the absence of tension-oriented cell divisions and in the presence of increased tissue tension, EVL cells undergo ectopic fusions, suggesting that the reduction of tension anisotropy by oriented cell divisions is required to prevent EVL cells from fusing. We conclude that cell-division orientation by tension constitutes a key mechanism for limiting tension anisotropy and thus promoting tissue spreading during EVL epiboly.

Tolerating an infection: an indirect benefit of co-founding queen associations in the ant Lasius niger - Pull, Christopher; Hughes, William; Brown, Markus (Naturwissenschaften)
Pathogens exert a strong selection pressure on organisms to evolve effective immune defences. In addition to individual immunity, social organisms can act cooperatively to produce collective defences. In many ant species, queens have the option to found a colony alone or in groups with other, often unrelated, conspecifics. These associations are transient, usually lasting only as long as each queen benefits from the presence of others. In fact, once the first workers emerge, queens fight to the death for dominance. One potential advantage of co-founding may be that queens benefit from collective disease defences, such as mutual grooming, that act against common soil pathogens. We test this hypothesis by exposing single and co-founding queens to a fungal parasite, in order to assess whether queens in co-founding associations have improved survival. Surprisingly, co-foundresses exposed to the entomopathogenic fungus Metarhizium did not engage in cooperative disease defences, and consequently, we find no direct benefit of multiple queens on survival. However, an indirect benefit was observed, with parasite-exposed queens producing more brood when they co-founded, than when they were alone. We suggest this is due to a trade-off between reproduction and immunity. Additionally, we report an extraordinary ability of the queens to tolerate an infection for long periods after parasite exposure. Our study suggests that there are no social immunity benefits for co-founding ant queens, but that in parasite-rich environments, the presence of additional queens may nevertheless improve the chances of colony founding success.

The force and effect of cell proliferation - Campinho, Pedro; Heisenberg, Carl-Philipp J (EMBO Journal)
The spatiotemporal control of cell divisions is a key factor in epithelial morphogenesis and patterning. Mao et al (2013) now describe how differential rates of proliferation within the Drosophila wing disc epithelium give rise to anisotropic tissue tension in peripheral/proximal regions of the disc. Such global tissue tension anisotropy in turn determines the orientation of cell divisions by controlling epithelial cell elongation.

Quantitative reactive modeling and verification - Henzinger, Thomas A (Computer Science Research and Development)
Formal verification aims to improve the quality of software by detecting errors before they do harm. At the basis of formal verification is the logical notion of correctness, which purports to capture whether or not a program behaves as desired. We suggest that the boolean partition of software into correct and incorrect programs falls short of the practical need to assess the behavior of software in a more nuanced fashion against multiple criteria. We therefore propose to introduce quantitative fitness measures for programs, specifically for measuring the function, performance, and robustness of reactive programs such as concurrent processes. This article describes the goals of the ERC Advanced Investigator Project QUAREM. The project aims to build and evaluate a theory of quantitative fitness measures for reactive models. Such a theory must strive to obtain quantitative generalizations of the paradigms that have been success stories in qualitative reactive modeling, such as compositionality, property-preserving abstraction and abstraction refinement, model checking, and synthesis. The theory will be evaluated not only in the context of software and hardware engineering, but also in the context of systems biology. In particular, we will use the quantitative reactive models and fitness measures developed in this project for testing hypotheses about the mechanisms behind data from biological experiments.

ECHIDNA mediated post Golgi trafficking of auxin carriers for differential cell elongation - Boutté, Yohann; Jonsson, Kristoffer; Mcfarlane, Heather; Johnson, Errin; Gendre, Delphine; Swarup, Ranjan; Friml, Jirí; Samuels, Lacey; Robert, Stéphanie; Bhalerao, Rishikesh (PNAS)
The plant hormone indole-acetic acid (auxin) is essential for many aspects of plant development. Auxin-mediated growth regulation typically involves the establishment of an auxin concentration gradient mediated by polarly localized auxin transporters. The localization of auxin carriers and their amount at the plasma membrane are controlled by membrane trafficking processes such as secretion, endocytosis, and recycling. In contrast to endocytosis or recycling, how the secretory pathway mediates the localization of auxin carriers is not well understood. In this study we have used the differential cell elongation process during apical hook development to elucidate the mechanisms underlying the post-Golgi trafficking of auxin carriers in Arabidopsis. We show that differential cell elongation during apical hook development is defective in Arabidopsis mutant echidna (ech). ECH protein is required for the trans-Golgi network (TGN)-mediated trafficking of the auxin influx carrier AUX1 to the plasma membrane. In contrast, ech mutation only marginally perturbs the trafficking of the highly related auxin influx carrier LIKE-AUX1-3 or the auxin efflux carrier PIN-FORMED-3, both also involved in hook development. Electron tomography reveals that the trafficking defects in ech mutant are associated with the perturbation of secretory vesicle genesis from the TGN. Our results identify differential mechanisms for the post-Golgi trafficking of de novo-synthesized auxin carriers to plasma membrane from the TGN and reveal how trafficking of auxin influx carriers mediates the control of differential cell elongation in apical hook development.

Drosophila Embryo Stage Annotation using Label Propagation - Kazmar, Tomas; Kvon, Evgeny; Stark, Alexander; Lampert, Christoph
In this work we propose a system for automatic classification of Drosophila embryos into developmental stages. While the system is designed to solve an actual problem in biological research, we believe that the principle underly- ing it is interesting not only for biologists, but also for researchers in computer vision. The main idea is to combine two orthogonal sources of information: one is a classifier trained on strongly invariant features, which makes it applicable to images of very different conditions, but also leads to rather noisy predictions. The other is a label propagation step based on a more powerful similarity measure that however is only consistent within specific subsets of the data at a time. In our biological setup, the information sources are the shape and the staining patterns of embryo images. We show experimentally that while neither of the methods can be used by itself to achieve satisfactory results, their combina- tion achieves prediction quality comparable to human performance.

Mathematical Foundations of Computer Science 2013
This book constitutes the thoroughly refereed conference proceedings of the 38th International Symposium on Mathematical Foundations of Computer Science, MFCS 2013, held in Klosterneuburg, Austria, in August 2013. The 67 revised full papers presented together with six invited talks were carefully selected from 191 submissions. Topics covered include algorithmic game theory, algorithmic learning theory, algorithms and data structures, automata, formal languages, bioinformatics, complexity, computational geometry, computer-assisted reasoning, concurrency theory, databases and knowledge-based systems, foundations of computing, logic in computer science, models of computation, semantics and verification of programs, and theoretical issues in artificial intelligence.

Learning to rank using privileged information - Sharmanska, Viktoriia; Quadrianto, Novi; Lampert, Christoph
Many computer vision problems have an asymmetric distribution of information between training and test time. In this work, we study the case where we are given additional information about the training data, which however will not be available at test time. This situation is called learning using privileged information (LUPI). We introduce two maximum-margin techniques that are able to make use of this additional source of information, and we show that the framework is applicable to several scenarios that have been studied in computer vision before. Experiments with attributes, bounding boxes, image tags and rationales as additional information in object classification show promising results.

Cryptographically enforced RBAC - Ferrara, Anna; Fuchsbauer, Georg; Warinschi, Bogdan
Cryptographic access control promises to offer easily distributed trust and broader applicability, while reducing reliance on low-level online monitors. Traditional implementations of cryptographic access control rely on simple cryptographic primitives whereas recent endeavors employ primitives with richer functionality and security guarantees. Worryingly, few of the existing cryptographic access-control schemes come with precise guarantees, the gap between the policy specification and the implementation being analyzed only informally, if at all. In this paper we begin addressing this shortcoming. Unlike prior work that targeted ad-hoc policy specification, we look at the well-established Role-Based Access Control (RBAC) model, as used in a typical file system. In short, we provide a precise syntax for a computational version of RBAC, offer rigorous definitions for cryptographic policy enforcement of a large class of RBAC security policies, and demonstrate that an implementation based on attribute-based encryption meets our security notions. We view our main contribution as being at the conceptual level. Although we work with RBAC for concreteness, our general methodology could guide future research for uses of cryptography in other access-control models.

Computational Methods in Systems Biology
This book constitutes the proceedings of the 11th International Conference on Computational Methods in Systems Biology, CMSB 2013, held in Klosterneuburg, Austria, in September 2013. The 15 regular papers included in this volume were carefully reviewed and selected from 27 submissions. They deal with computational models for all levels, from molecular and cellular, to organs and entire organisms.

Local shape analysis for overlaid data structures - Dragoi, Cezara; Enea, Constantin; Sighireanu, Mihaela
We present a shape analysis for programs that manipulate overlaid data structures which share sets of objects. The abstract domain contains Separation Logic formulas that (1) combine a per-object separating conjunction with a per-field separating conjunction and (2) constrain a set of variables interpreted as sets of objects. The definition of the abstract domain operators is based on a notion of homomorphism between formulas, viewed as graphs, used recently to define optimal decision procedures for fragments of the Separation Logic. Based on a Frame Rule that supports the two versions of the separating conjunction, the analysis is able to reason in a modular manner about non-overlaid data structures and then, compose information only at a few program points, e.g., procedure returns. We have implemented this analysis in a prototype tool and applied it on several interesting case studies that manipulate overlaid and nested linked lists.

Synthesis of AMBA AHB from formal specification: A case study - Godhal, Yashdeep; Chatterjee, Krishnendu; Henzinger, Thomas A (International Journal on Software Tools for Technology Transfer)
The standard hardware design flow involves: (a) design of an integrated circuit using a hardware description language, (b) extensive functional and formal verification, and (c) logical synthesis. However, the above-mentioned processes consume significant effort and time. An alternative approach is to use a formal specification language as a high-level hardware description language and synthesize hardware from formal specifications. Our work is a case study of the synthesis of the widely and industrially used AMBA AHB protocol from formal specifications. Bloem et al. presented the first formal specifications for the AMBA AHB Arbiter and synthesized the AHB Arbiter circuit. However, in the first formal specification some important assumptions were missing. Our contributions are as follows: (a) We present detailed formal specifications for the AHB Arbiter incorporating the missing details, and obtain significant improvements in the synthesis results (both with respect to the number of gates in the synthesized circuit and with respect to the time taken to synthesize the circuit), and (b) we present formal specifications to generate compact circuits for the remaining two main components of AMBA AHB, namely, AHB Master and AHB Slave. Thus with systematic description we are able to automatically and completely synthesize an important and widely used industrial protocol.

Hot topics in cold gases: A mathematical physics perspective - Seiringer, Robert (Japanese Journal of Mathematics)
We present an overview of mathematical results on the low temperature properties of dilute quantum gases, which have been obtained in the past few years. The presentation includes a discussion of Bose-Einstein condensation, the excitation spectrum for trapped gases and its relation to superfluidity, as well as the appearance of quantized vortices in rotating systems. All these properties are intensely being studied in current experiments on cold atomic gases. We will give a description of the mathematics involved in understanding these phenomena, starting from the underlying many-body Schrödinger equation.

(Open) Linked Data in Bibliotheken - Danowski, Patrick; Pohl, Adrian
Das Buch ist sowohl eine Einführung in die Themen Linked Data, Open Data und Open Linked Data als es auch den konkreten Bezug auf Bibliotheken behandelt. Hierzu werden konkrete Anwendungsprojekte beschrieben. Der Band wendet sich dabei sowohl an Personen aus der Bibliothekspraxis als auch an Personen aus dem Bibliotheksmanagement, die noch nicht mit dem Thema vertraut sind.

P: Safe asynchronous event-driven programming - Desai, Ankush; Gupta, Vivek; Jackson, Ethan; Qadeer, Shaz; Rajamani, Sriram; Zufferey, Damien (Proceedings of the 34th ACM SIGPLAN Conference on Programming Language Design and Implementation)
We describe the design and implementation of P, a domain-specific language to write asynchronous event driven code. P allows the programmer to specify the system as a collection of interacting state machines, which communicate with each other using events. P unifies modeling and programming into one activity for the programmer. Not only can a P program be compiled into executable code, but it can also be tested using model checking techniques. P allows the programmer to specify the environment, used to "close" the system during testing, as nondeterministic ghost machines. Ghost machines are erased during compilation to executable code; a type system ensures that the erasure is semantics preserving. The P language is designed so that a P program can be checked for responsiveness-the ability to handle every event in a timely manner. By default, a machine needs to handle every event that arrives in every state. But handling every event in every state is impractical. The language provides a notion of deferred events where the programmer can annotate when she wants to delay processing an event. The default safety checker looks for presence of unhan-dled events. The language also provides default liveness checks that an event cannot be potentially deferred forever. P was used to implement and verify the core of the USB device driver stack that ships with Microsoft Windows 8. The resulting driver is more reliable and performs better than its prior incarnation (which did not use P); we have more confidence in the robustness of its design due to the language abstractions and verification provided by P.

Realization of stripes and slabs in two and three dimensions - Giuliani, Alessandro; Lieb, Élliott; Seiringer, Robert (Physical Review B)
We consider Ising models in two and three dimensions with nearest neighbor ferromagnetic interactions and long-range, power law decaying, antiferromagnetic interactions. If the strength of the ferromagnetic coupling J is larger than a critical value Jc, then the ground state is homogeneous and ferromagnetic. As the critical value is approached from smaller values of J, it is believed that the ground state consists of a periodic array of stripes (d=2) or slabs (d=3), all of the same size and alternating magnetization. Here we prove rigorously that the ground state energy per site converges to that of the optimal periodic striped or slabbed state, in the limit that J tends to the ferromagnetic transition point. While this theorem does not prove rigorously that the ground state is precisely striped or slabbed, it does prove that in any suitably large box the ground state is striped or slabbed with high probability.

Dissection of gene function at clonal level using mosaic analysis with double markers - Hippenmeyer, Simon (Frontiers in Biology)
MADM (Mosaic Analysis with Double Markers) technology offers a genetic approach in mice to visualize and concomitantly manipulate genetically defined cells at clonal level and single cell resolution. MADM employs Cre recombinase/loxP-dependent interchromosomal mitotic recombination to reconstitute two split marker genes—green GFP and red tdTomato—and can label sparse clones of homozygous mutant cells in one color and wild-type cells in the other color in an otherwise unlabeled background. At present, major MADM applications include lineage tracing, single cell labeling, conditional knockouts in small populations of cells and induction of uniparental chromosome disomy to assess effects of genomic imprinting. MADM can be applied universally in the mouse with the sole limitation being the specificity of the promoter controlling Cre recombinase expression. Here I review recent developments and extensions of the MADM technique and give an overview of the major discoveries and progresses enabled by the implementation of the novel genetic MADM tools.

Van der Corput sequences and linear permutations - Pausinger, Florian (Electronic Notes in Discrete Mathematics)
This extended abstract is concerned with the irregularities of distribution of one-dimensional permuted van der Corput sequences that are generated from linear permutations. We show how to obtain upper bounds for the discrepancy and diaphony of these sequences, by relating them to Kronecker sequences and applying earlier results of Faure and Niederreiter.

Aspect-oriented linearizability proofs - Henzinger, Thomas A; Sezgin, Ali; Vafeiadis, Viktor
Linearizability of concurrent data structures is usually proved by monolithic simulation arguments relying on identifying the so-called linearization points. Regrettably, such proofs, whether manual or automatic, are often complicated and scale poorly to advanced non-blocking concurrency patterns, such as helping and optimistic updates. In response, we propose a more modular way of checking linearizability of concurrent queue algorithms that does not involve identifying linearization points. We reduce the task of proving linearizability with respect to the queue specification to establishing four basic properties, each of which can be proved independently by simpler arguments. As a demonstration of our approach, we verify the Herlihy and Wing queue, an algorithm that is challenging to verify by a simulation proof.

Probabilistic models for CRISPR spacer content evolution - Kupczok, Anne; Bollback, Jonathan P (BMC Evolutionary Biology)
Background: The CRISPR/Cas system is known to act as an adaptive and heritable immune system in Eubacteria and Archaea. Immunity is encoded in an array of spacer sequences. Each spacer can provide specific immunity to invasive elements that carry the same or a similar sequence. Even in closely related strains, spacer content is very dynamic and evolves quickly. Standard models of nucleotide evolutioncannot be applied to quantify its rate of change since processes other than single nucleotide changes determine its evolution.Methods We present probabilistic models that are specific for spacer content evolution. They account for the different processes of insertion and deletion. Insertions can be constrained to occur on one end only or are allowed to occur throughout the array. One deletion event can affect one spacer or a whole fragment of adjacent spacers. Parameters of the underlying models are estimated for a pair of arrays by maximum likelihood using explicit ancestor enumeration.Results Simulations show that parameters are well estimated on average under the models presented here. There is a bias in the rate estimation when including fragment deletions. The models also estimate times between pairs of strains. But with increasing time, spacer overlap goes to zero, and thus there is an upper bound on the distance that can be estimated. Spacer content similarities are displayed in a distance based phylogeny using the estimated times.We use the presented models to analyze different Yersinia pestis data sets and find that the results among them are largely congruent. The models also capture the variation in diversity of spacers among the data sets. A comparison of spacer-based phylogenies and Cas gene phylogenies shows that they resolve very different time scales for this data set.Conclusions The simulations and data analyses show that the presented models are useful for quantifying spacer content evolution and for displaying spacer content similarities of closely related strains in a phylogeny. This allows for comparisons of different CRISPR arrays or for comparisons between CRISPR arrays and nucleotide substitution rates.

Neuronal oscillations scale up and scale down the brain dynamics - Valderrama, Mario; Botella Soler, Vicente; Le Van Quyen, Michel (Multiscale Analysis and Nonlinear Dynamics: From Genes to the Brain)
Progress in understanding the global brain dynamics has remained slow to date in large part because of the highly multiscale nature of brain activity. Indeed, normal brain dynamics is characterized by complex interactions between multiple levels: from the microscopic scale of single neurons to the mesoscopic level of local groups of neurons, and finally to the macroscopic level of the whole brain. Among the most difficult tasks are those of identifying which scales are significant for a given particular function and describing how the scales affect each other. It is important to realize that the scales of time and space are linked together, or even intertwined, and that causal inference is far more ambiguous between than within levels. We approach this problem from the perspective of our recent work on simultaneous recording from micro- and macroelectrodes in the human brain. We propose a physiological description of these multilevel interactions, based on phase–amplitude coupling of neuronal oscillations that operate at multiple frequencies and on different spatial scales. Specifically, the amplitude of the oscillations on a particular spatial scale is modulated by phasic variations in neuronal excitability induced by lower frequency oscillations that emerge on a larger spatial scale. Following this general principle, it is possible to scale up or scale down the multiscale brain dynamics. It is expected that large-scale network oscillations in the low-frequency range, mediating downward effects, may play an important role in attention and consciousness.

Complete genome sequence of the novel phage MG-B1 infecting bacillus weihenstephanensis - Fernandes Redondo, Rodrigo A; Kupczok, Anne; Stift, Gertraud; Bollback, Jonathan P (Genome Announcements)
Here, we describe a novel virulent bacteriophage that infects Bacillus weihenstephanensis, isolated from soil in Austria. It is the first phage to be discovered that infects this species. Here, we present the complete genome sequence of this podovirus.

Automating separation logic using SMT - Piskac, Ruzica; Wies, Thomas; Zufferey, Damien
Separation logic (SL) has gained widespread popularity because of its ability to succinctly express complex invariants of a program’s heap configurations. Several specialized provers have been developed for decidable SL fragments. However, these provers cannot be easily extended or combined with solvers for other theories that are important in program verification, e.g., linear arithmetic. In this paper, we present a reduction of decidable SL fragments to a decidable first-order theory that fits well into the satisfiability modulo theories (SMT) framework. We show how to use this reduction to automate satisfiability, entailment, frame inference, and abduction problems for separation logic using SMT solvers. Our approach provides a simple method of integrating separation logic into existing verification tools that provide SMT backends, and an elegant way of combining SL fragments with other decidable first-order theories. We implemented this approach in a verification tool and applied it to heap-manipulating programs whose verification involves reasoning in theory combinations.

Defining the selectivity of processes along the auxin response chain: A study using auxin analogues - Simon, Sibu; Kubeš, Martin; Baster, Pawel; Robert, Stéphanie; Dobrev, Petre; Friml, Jirí; Petrášek, Jan; Zažímalová, Eva (New Phytologist)
The mode of action of auxin is based on its non-uniform distribution within tissues and organs. Despite the wide use of several auxin analogues in research and agriculture, little is known about the specificity of different auxin-related transport and signalling processes towards these compounds. Using seedlings of Arabidopsis thaliana and suspension-cultured cells of Nicotiana tabacum (BY-2), the physiological activity of several auxin analogues was investigated, together with their capacity to induce auxin-dependent gene expression, to inhibit endocytosis and to be transported across the plasma membrane. This study shows that the specificity criteria for different auxin-related processes vary widely. Notably, the special behaviour of some synthetic auxin analogues suggests that they might be useful tools in investigations of the molecular mechanism of auxin action. Thus, due to their differential stimulatory effects on DR5 expression, indole-3-propionic (IPA) and 2,4,5-trichlorophenoxy acetic (2,4,5-T) acids can serve in studies of TRANSPORT INHIBITOR RESPONSE 1/AUXIN SIGNALLING F-BOX (TIR1/AFB)-mediated auxin signalling, and 5-fluoroindole-3-acetic acid (5-F-IAA) can help to discriminate between transcriptional and non-transcriptional pathways of auxin signalling. The results demonstrate that the major determinants for the auxin-like physiological potential of a particular compound are very complex and involve its chemical and metabolic stability, its ability to distribute in tissues in a polar manner and its activity towards auxin signalling machinery.

Automata with generalized Rabin pairs for probabilistic model checking and LTL synthesis - Chatterjee, Krishnendu; Gaiser, Andreas; Kretinsky, Jan
The model-checking problem for probabilistic systems crucially relies on the translation of LTL to deterministic Rabin automata (DRW). Our recent Safraless translation [KE12, GKE12] for the LTL(F,G) fragment produces smaller automata as compared to the traditional approach. In this work, instead of DRW we consider deterministic automata with acceptance condition given as disjunction of generalized Rabin pairs (DGRW). The Safraless translation of LTL(F,G) formulas to DGRW results in smaller automata as compared to DRW. We present algorithms for probabilistic model-checking as well as game solving for DGRW conditions. Our new algorithms lead to improvement both in terms of theoretical bounds as well as practical evaluation. We compare PRISM with and without our new translation, and show that the new translation leads to significant improvements.

Faster algorithms for Markov decision processes with low treewidth - Chatterjee, Krishnendu; Ła̧Cki, Jakub
We consider two core algorithmic problems for probabilistic verification: the maximal end-component decomposition and the almost-sure reachability set computation for Markov decision processes (MDPs). For MDPs with treewidth k, we present two improved static algorithms for both the problems that run in time O(n·k 2.38·2k ) and O(m·logn· k), respectively, where n is the number of states and m is the number of edges, significantly improving the previous known O(n·k·√n· k) bound for low treewidth. We also present decremental algorithms for both problems for MDPs with constant treewidth that run in amortized logarithmic time, which is a huge improvement over the previously known algorithms that require amortized linear time.

Retromer subunits VPS35A and VPS29 mediate prevacuolar compartment (PVC) function in Arabidopsis - Nodzyński, Tomasz; Feraru, Murguel; Hirsch, Sibylle; De Rycke, Riet; Nicuales, Claudiu; Van Leene, Jelle; De Jaeger, Geert; Vanneste, Steffen; Friml, Jirí (Molecular Plant)
Intracellular protein routing is mediated by vesicular transport which is tightly regulated in eukaryotes. The protein and lipid homeostasis depends on coordinated delivery of de novo synthesized or recycled cargoes to the plasma membrane by exocytosis and their subsequent removal by rerouting them for recycling or degradation. Here, we report the characterization of protein affected trafficking 3 (pat3) mutant that we identified by an epifluorescence-based forward genetic screen for mutants defective in subcellular distribution of Arabidopsis auxin transporter PIN1–GFP. While pat3 displays largely normal plant morphology and development in nutrient-rich conditions, it shows strong ectopic intracellular accumulations of different plasma membrane cargoes in structures that resemble prevacuolar compartments (PVC) with an aberrant morphology. Genetic mapping revealed that pat3 is defective in vacuolar protein sorting 35A (VPS35A), a putative subunit of the retromer complex that mediates retrograde trafficking between the PVC and trans-Golgi network. Similarly, a mutant defective in another retromer subunit, vps29, shows comparable subcellular defects in PVC morphology and protein accumulation. Thus, our data provide evidence that the retromer components VPS35A and VPS29 are essential for normal PVC morphology and normal trafficking of plasma membrane proteins in plants. In addition, we show that, out of the three VPS35 retromer subunits present in Arabidopsis thaliana genome, the VPS35 homolog A plays a prevailing role in trafficking to the lytic vacuole, presenting another level of complexity in the retromer-dependent vacuolar sorting.

Mechanism of protein kinetic stabilization by engineered disulfide crosslinks - Sanchez Romero, Inmaculada; Ariza, Antonio; Wilson, Keith; Skjøt, Michael; Vind, Jesper; De Maria, Leonardo; Skov, Lars; Sánchez Ruiz, Jose (PLoS One)
The impact of disulfide bonds on protein stability goes beyond simple equilibrium thermodynamics effects associated with the conformational entropy of the unfolded state. Indeed, disulfide crosslinks may play a role in the prevention of dysfunctional association and strongly affect the rates of irreversible enzyme inactivation, highly relevant in biotechnological applications. While these kinetic-stability effects remain poorly understood, by analogy with proposed mechanisms for processes of protein aggregation and fibrillogenesis, we propose that they may be determined by the properties of sparsely-populated, partially-unfolded intermediates. Here we report the successful design, on the basis of high temperature molecular-dynamics simulations, of six thermodynamically and kinetically stabilized variants of phytase from Citrobacter braakii (a biotechnologically important enzyme) with one, two or three engineered disulfides. Activity measurements and 3D crystal structure determination demonstrate that the engineered crosslinks do not cause dramatic alterations in the native structure. The inactivation kinetics for all the variants displays a strongly non-Arrhenius temperature dependence, with the time-scale for the irreversible denaturation process reaching a minimum at a given temperature within the range of the denaturation transition. We show this striking feature to be a signature of a key role played by a partially unfolded, intermediate state/ensemble. Energetic and mutational analyses confirm that the intermediate is highly unfolded (akin to a proposed critical intermediate in the misfolding of the prion protein), a result that explains the observed kinetic stabilization. Our results provide a rationale for the kinetic-stability consequences of disulfide-crosslink engineering and an experimental methodology to arrive at energetic/structural descriptions of the sparsely populated and elusive intermediates that play key roles in irreversible protein denaturation.

Role of the Arabidopsis PIN6 auxin transporter in auxin homeostasis and auxin-mediated development - Cazzonelli, Christopher; Vanstraelen, Marleen; Simon, Sibu; Yin, Kuide; Carron Arthur, Ashley; Nisar, Nazia; Tarle, Gauri; Cuttriss, Abby; Searle, Iain; Benková, Eva; Mathesius, Ulrike; Masle, Josette; et al. (PLoS One)
Plant-specific PIN-formed (PIN) efflux transporters for the plant hormone auxin are required for tissue-specific directional auxin transport and cellular auxin homeostasis. The Arabidopsis PIN protein family has been shown to play important roles in developmental processes such as embryogenesis, organogenesis, vascular tissue differentiation, root meristem patterning and tropic growth. Here we analyzed roles of the less characterised Arabidopsis PIN6 auxin transporter. PIN6 is auxin-inducible and is expressed during multiple auxin-regulated developmental processes. Loss of pin6 function interfered with primary root growth and lateral root development. Misexpression of PIN6 affected auxin transport and interfered with auxin homeostasis in other growth processes such as shoot apical dominance, lateral root primordia development, adventitious root formation, root hair outgrowth and root waving. These changes in auxin-regulated growth correlated with a reduction in total auxin transport as well as with an altered activity of DR5-GUS auxin response reporter. Overall, the data indicate that PIN6 regulates auxin homeostasis during plant development.

Overexpression of the auxin binding PROTEIN1 modulates PIN-dependent auxin transport in tobacco cells - Čovanová, Milada; Sauer, Michael; Rychtář, Jan; Friml, Jirí; Petrášek, Jan; Zažímalová, Eva (PLoS One)
Background:Auxin binding protein 1 (ABP1) is a putative auxin receptor and its function is indispensable for plant growth and development. ABP1 has been shown to be involved in auxin-dependent regulation of cell division and expansion, in plasma-membrane-related processes such as changes in transmembrane potential, and in the regulation of clathrin-dependent endocytosis. However, the ABP1-regulated downstream pathway remains elusive.Methodology/Principal Findings:Using auxin transport assays and quantitative analysis of cellular morphology we show that ABP1 regulates auxin efflux from tobacco BY-2 cells. The overexpression of ABP1can counterbalance increased auxin efflux and auxin starvation phenotypes caused by the overexpression of PIN auxin efflux carrier. Relevant mechanism involves the ABP1-controlled vesicle trafficking processes, including positive regulation of endocytosis of PIN auxin efflux carriers, as indicated by fluorescence recovery after photobleaching (FRAP) and pharmacological manipulations.Conclusions/Significance:The findings indicate the involvement of ABP1 in control of rate of auxin transport across plasma membrane emphasizing the role of ABP1 in regulation of PIN activity at the plasma membrane, and highlighting the relevance of ABP1 for the formation of developmentally important, PIN-dependent auxin gradients.

Highly adaptive liquid simulations on tetrahedral meshes - Ando, Ryoichi; Thuerey, Nils; Wojtan, Christopher J (ACM Transactions on Graphics)
We introduce a new method for efficiently simulating liquid with extreme amounts of spatial adaptivity. Our method combines several key components to drastically speed up the simulation of large-scale fluid phenomena: We leverage an alternative Eulerian tetrahedral mesh discretization to significantly reduce the complexity of the pressure solve while increasing the robustness with respect to element quality and removing the possibility of locking. Next, we enable subtle free-surface phenomena by deriving novel second-order boundary conditions consistent with our discretization. We couple this discretization with a spatially adaptive Fluid-Implicit Particle (FLIP) method, enabling efficient, robust, minimally-dissipative simulations that can undergo sharp changes in spatial resolution while minimizing artifacts. Along the way, we provide a new method for generating a smooth and detailed surface from a set of particles with variable sizes. Finally, we explore several new sizing functions for determining spatially adaptive simulation resolutions, and we show how to couple them to our simulator. We combine each of these elements to produce a simulation algorithm that is capable of creating animations at high maximum resolutions while avoiding common pitfalls like inaccurate boundary conditions and inefficient computation.

Putting holes in holey geometry: Topology change for arbitrary surfaces - Bernstein, Gilbert; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper presents a method for computing topology changes for triangle meshes in an interactive geometric modeling environment. Most triangle meshes in practice do not exhibit desirable geometric properties, so we develop a solution that is independent of standard assumptions and robust to geometric errors. Specifically, we provide the first method for topology change applicable to arbitrary non-solid, non-manifold, non-closed, self-intersecting surfaces. We prove that this new method for topology change produces the expected conventional results when applied to solid (closed, manifold, non-self-intersecting) surfaces---that is, we prove a backwards-compatibility property relative to prior work. Beyond solid surfaces, we present empirical evidence that our method remains tolerant to a variety of surface aberrations through the incorporation of a novel error correction scheme. Finally, we demonstrate how topology change applied to non-solid objects enables wholly new and useful behaviors.

Liquid surface tracking with error compensation - Bojsen-Hansen, Morten; Wojtan, Christopher J (ACM Transactions on Graphics)
Our work concerns the combination of an Eulerian liquid simulation with a high-resolution surface tracker (e.g. the level set method or a Lagrangian triangle mesh). The naive application of a high-resolution surface tracker to a low-resolution velocity field can produce many visually disturbing physical and topological artifacts that limit their use in practice. We address these problems by defining an error function which compares the current state of the surface tracker to the set of physically valid surface states. By reducing this error with a gradient descent technique, we introduce a novel physics-based surface fairing method. Similarly, by treating this error function as a potential energy, we derive a new surface correction force that mimics the vortex sheet equations. We demonstrate our results with both level set and mesh-based surface trackers.

Three functions of cadherins in cell adhesion - Maître, Jean-Léon; Heisenberg, Carl-Philipp J (Current Biology)
Cadherins are transmembrane proteins that mediate cell–cell adhesion in animals. By regulating contact formation and stability, cadherins play a crucial role in tissue morphogenesis and homeostasis. Here, we review the three major unctions of cadherins in cell–cell contact formation and stability. Two of those functions lead to a decrease in interfacial ension at the forming cell–cell contact, thereby promoting contact expansion — first, by providing adhesion tension that lowers interfacial tension at the cell–cell contact, and second, by signaling to the actomyosin cytoskeleton in order to reduce cortex tension and thus interfacial tension at the contact. The third function of cadherins in cell–cell contact formation is to stabilize the contact by resisting mechanical forces that pull on the contact.

Genetic hitch-hiking in spatially extended populations - Barton, Nicholas H; Etheridge, Alison; Kelleher, Jerome; Véber, Amandine (Theoretical Population Biology)
When a mutation with selective advantage s spreads through a panmictic population, it may cause two lineages at a linked locus to coalesce; the probability of coalescence is exp(−2rT), where T∼log(2Ns)/s is the time to fixation, N is the number of haploid individuals, and r is the recombination rate. Population structure delays fixation, and so weakens the effect of a selective sweep. However, favourable alleles spread through a spatially continuous population behind a narrow wavefront; ancestral lineages are confined at the tip of this front, and so coalesce rapidly. In extremely dense populations, coalescence is dominated by rare fluctuations ahead of the front. However, we show that for moderate densities, a simple quasi-deterministic approximation applies: the rate of coalescence within the front is λ∼2g(η)/(ρℓ), where ρ is the population density and is the characteristic scale of the wavefront; g(η) depends only on the strength of random drift, . The net effect of a sweep on coalescence also depends crucially on whether two lineages are ever both within the wavefront at the same time: even in the extreme case when coalescence within the front is instantaneous, the net rate of coalescence may be lower than in a single panmictic population. Sweeps can also have a substantial impact on the rate of gene flow. A single lineage will jump to a new location when it is hit by a sweep, with mean square displacement ; this can be substantial if the species’ range, L, is large, even if the species-wide rate of sweeps per map length, Λ/R, is small. This effect is half as strong in two dimensions. In contrast, the rate of coalescence between lineages, at random locations in space and on the genetic map, is proportional to (c/L)(Λ/R), where c is the wavespeed: thus, on average, one-dimensional structure is likely to reduce coalescence due to sweeps, relative to panmixis. In two dimensions, genes must move along the front before they can coalesce; this process is rapid, being dominated by rare fluctuations. This leads to a dramatically higher rate of coalescence within the wavefront than if lineages simply diffused along the front. Nevertheless, the net rate of coalescence due to a sweep through a two-dimensional population is likely to be lower than it would be with panmixis.

Formalizing and reasoning about quality - Almagor, Shaull; Boker, Udi; Kupferman, Orna
Traditional formal methods are based on a Boolean satisfaction notion: a reactive system satisfies, or not, a given specification. We generalize formal methods to also address the quality of systems. As an adequate specification formalism we introduce the linear temporal logic LTL[F]. The satisfaction value of an LTL[F] formula is a number between 0 and 1, describing the quality of the satisfaction. The logic generalizes traditional LTL by augmenting it with a (parameterized) set F of arbitrary functions over the interval [0,1]. For example, F may contain the maximum or minimum between the satisfaction values of subformulas, their product, and their average. The classical decision problems in formal methods, such as satisfiability, model checking, and synthesis, are generalized to search and optimization problems in the quantitative setting. For example, model checking asks for the quality in which a specification is satisfied, and synthesis returns a system satisfying the specification with the highest quality. Reasoning about quality gives rise to other natural questions, like the distance between specifications. We formalize these basic questions and study them for LTL[F]. By extending the automata-theoretic approach for LTL to a setting that takes quality into an account, we are able to solve the above problems and show that reasoning about LTL[F] has roughly the same complexity as reasoning about traditional LTL.

The power of linear programming for finite-valued CSPs: A constructive characterization - Kolmogorov, Vladimir
A class of valued constraint satisfaction problems (VCSPs) is characterised by a valued constraint language, a fixed set of cost functions on a finite domain. An instance of the problem is specified by a sum of cost functions from the language with the goal to minimise the sum. We study which classes of finite-valued languages can be solved exactly by the basic linear programming relaxation (BLP). Thapper and Živný showed [20] that if BLP solves the language then the language admits a binary commutative fractional polymorphism. We prove that the converse is also true. This leads to a necessary and a sufficient condition which can be checked in polynomial time for a given language. In contrast, the previous necessary and sufficient condition due to [20] involved infinitely many inequalities. More recently, Thapper and Živný [21] showed (using, in particular, a technique introduced in this paper) that core languages that do not satisfy our condition are NP-hard. Taken together, these results imply that a finite-valued language can either be solved using Linear Programming or is NP-hard.

Attribute-based classification for zero-shot learning of object categories - Lampert, Christoph; Nickisch, Hannes; Harmeling, Stefan (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We study the problem of object recognition for categories for which we have no training examples, a task also called zero-data or zero-shot learning. This situation has hardly been studied in computer vision research, even though it occurs frequently: the world contains tens of thousands of different object classes and for only few of them image collections have been formed and suitably annotated. To tackle the problem we introduce attribute-based classification: objects are identified based on a high-level description that is phrased in terms of semantic attributes, such as the object's color or shape. Because the identification of each such property transcends the specific learning task at hand, the attribute classifiers can be pre-learned independently, e.g. from existing image datasets unrelated to the current task. Afterwards, new classes can be detected based on their attribute representation, without the need for a new training phase. In this paper we also introduce a new dataset, Animals with Attributes, of over 30,000 images of 50 animal classes, annotated with 85 semantic attributes. Extensive experiments on this and two more datasets show that attribute-based classification indeed is able to categorize images without access to any training images of the target classes.

The supervised IBP: Neighbourhood preserving infinite latent feature models - Quadrianto, Novi; Sharmanska, Viktoriia; Knowles, David; Ghahramani, Zoubin (Proceedings of the 29th conference uncertainty in Artificial Intelligence)
We propose a probabilistic model to infer supervised latent variables in the Hamming space from observed data. Our model allows simultaneous inference of the number of binary latent variables, and their values. The latent variables preserve neighbourhood structure of the data in a sense that objects in the same semantic concept have similar latent values, and objects in different concepts have dissimilar latent values. We formulate the supervised infinite latent variable problem based on an intuitive principle of pulling objects together if they are of the same type, and pushing them apart if they are not. We then combine this principle with a flexible Indian Buffet Process prior on the latent variables. We show that the inferred supervised latent variables can be directly used to perform a nearest neighbour search for the purpose of retrieval. We introduce a new application of dynamically extending hash codes, and show how to effectively couple the structure of the hash codes with continuously growing structure of the neighbourhood preserving infinite latent feature space.

Stability and semiclassics in self-generated fields - Erdös, László; Fournais, Søren; Solovej, Jan (Journal of the European Mathematical Society)
We consider non-interacting particles subject to a fixed external potential V and a self-generated magnetic field B. The total energy includes the field energy β∫B2 and we minimize over all particle states and magnetic fields. In the case of spin-1/2 particles this minimization leads to the coupled Maxwell-Pauli system. The parameter β tunes the coupling strength between the field and the particles and it effectively determines the strength of the field. We investigate the stability and the semiclassical asymptotics, h→0, of the total ground state energy E(β,h,V). The relevant parameter measuring the field strength in the semiclassical limit is κ=βh. We are not able to give the exact leading order semiclassical asymptotics uniformly in κ or even for fixed κ. We do however give upper and lower bounds on E with almost matching dependence on κ. In the simultaneous limit h→0 and κ→∞ we show that the standard non-magnetic Weyl asymptotics holds. The same result also holds for the spinless case, i.e. where the Pauli operator is replaced by the Schrödinger operator.

Can quantitative and population genetics help us understand evolutionary computation? - Barton, Nicholas H; Paixao, Tiago (Proceedings of the 15th annual conference on Genetic and evolutionary computation)
Even though both population and quantitative genetics, and evolutionary computation, deal with the same questions, they have developed largely independently of each other. I review key results from each field, emphasising those that apply independently of the (usually unknown) relation between genotype and phenotype. The infinitesimal model provides a simple framework for predicting the response of complex traits to selection, which in biology has proved remarkably successful. This allows one to choose the schedule of population sizes and selection intensities that will maximise the response to selection, given that the total number of individuals realised, C = ∑t Nt, is constrained. This argument shows that for an additive trait (i.e., determined by the sum of effects of the genes), the optimum population size and the maximum possible response (i.e., the total change in trait mean) are both proportional to √C.

Accumulation of spontaneous mutations in the ciliate Tetrahymena thermophila - Long, Hongan; Paixao, Tiago; Azevedo, Ricardo; Zufall, Rebecca (Genetics)
Knowledge of the rate and fitness effects of mutations is essential for understanding the process of evolution. Mutations are inherently difficult to study because they are rare and are frequently eliminated by natural selection. In the ciliate Tetrahymena thermophila, mutations can accumulate in the germline genome without being exposed to selection. We have conducted a mutation accumulation (MA) experiment in this species. Assuming that all mutations are deleterious and have the same effect, we estimate that the deleterious mutation rate per haploid germline genome per generation is U = 0.0047 (95% credible interval: 0.0015, 0.0125), and that germline mutations decrease fitness by s = 11% when expressed in a homozygous state (95% CI: 4.4%, 27%). We also estimate that deleterious mutations are partially recessive on average (h = 0.26; 95% CI: –0.022, 0.62) and that the rate of lethal mutations is <10% of the deleterious mutation rate. Comparisons between the observed evolutionary responses in the germline and somatic genomes and the results from individual-based simulations of MA suggest that the two genomes have similar mutational parameters. These are the first estimates of the deleterious mutation rate and fitness effects from the eukaryotic supergroup Chromalveolata and are within the range of those of other eukaryotes.

A variance decomposition approach to the analysis of genetic algorithms - Paixao, Tiago; Barton, Nicholas H (Proceedings of the 15th annual conference on Genetic and evolutionary computation)
Prediction of the evolutionary process is a long standing problem both in the theory of evolutionary biology and evolutionary computation (EC). It has long been realized that heritable variation is crucial to both the response to selection and the success of genetic algorithms. However, not all variation contributes in the same way to the response. Quantitative genetics has developed a large body of work trying to estimate and understand how different components of the variance in fitness in the population contribute to the response to selection. We illustrate how to apply some concepts of quantitative genetics to the analysis of genetic algorithms. In particular, we derive estimates for the short term prediction of the response to selection and we use variance decomposition to gain insight on local aspects of the landscape. Finally, we propose a new population based genetic algorithm that uses these methods to improve its operation.

Local eigenvalue density for general MANOVA matrices - Erdös, László; Farrell, Brendan (Journal of Statistical Physics)
We consider random n×n matrices of the form (XX*+YY*)^{-1/2}YY*(XX*+YY*)^{-1/2}, where X and Y have independent entries with zero mean and variance one. These matrices are the natural generalization of the Gaussian case, which are known as MANOVA matrices and which have joint eigenvalue density given by the third classical ensemble, the Jacobi ensemble. We show that, away from the spectral edge, the eigenvalue density converges to the limiting density of the Jacobi ensemble even on the shortest possible scales of order 1/n (up to log n factors). This result is the analogue of the local Wigner semicircle law and the local Marchenko-Pastur law for general MANOVA matrices.

Extending continuous maps: Polynomiality and undecidability - Čadek, Martin; Krcál, Marek; Matoušek, Jiří; Vokřínek, Lukáš; Wagner, Uli (45th Annual ACM Symposium on theory of computing)
We consider several basic problems of algebraic topology, with connections to combinatorial and geometric questions, from the point of view of computational complexity. The extension problem asks, given topological spaces X; Y , a subspace A ⊆ X, and a (continuous) map f : A → Y , whether f can be extended to a map X → Y . For computational purposes, we assume that X and Y are represented as finite simplicial complexes, A is a subcomplex of X, and f is given as a simplicial map. In this generality the problem is undecidable, as follows from Novikov's result from the 1950s on uncomputability of the fundamental group π1(Y ). We thus study the problem under the assumption that, for some k ≥ 2, Y is (k - 1)-connected; informally, this means that Y has \no holes up to dimension k-1" (a basic example of such a Y is the sphere Sk). We prove that, on the one hand, this problem is still undecidable for dimX = 2k. On the other hand, for every fixed k ≥ 2, we obtain an algorithm that solves the extension problem in polynomial time assuming Y (k - 1)-connected and dimX ≤ 2k - 1. For dimX ≤ 2k - 2, the algorithm also provides a classification of all extensions up to homotopy (continuous deformation). This relies on results of our SODA 2012 paper, and the main new ingredient is a machinery of objects with polynomial-time homology, which is a polynomial-time analog of objects with effective homology developed earlier by Sergeraert et al. We also consider the computation of the higher homotopy groups πk(Y ), k ≥ 2, for a 1-connected Y . Their computability was established by Brown in 1957; we show that πk(Y ) can be computed in polynomial time for every fixed k ≥ 2. On the other hand, Anick proved in 1989 that computing πk(Y ) is #P-hard if k is a part of input, where Y is a cell complex with certain rather compact encoding. We strengthen his result to #P-hardness for Y given as a simplicial complex.

The moss physcomitrella patens reproductive organ development is highly organized, affected by the two SHI/STY genes and by the level of active auxin in the SHI/STY expression domain - Landberg, Katarina; Pederson, Eric; Viaene, Tom; Bozorg, Behruz; Friml, Jirí; Jönsson, Henrik; Thelander, Mattias; Sundberg, Eva (Plant Physiology)
In order to establish a reference for analysis of the function of auxin and the auxin biosynthesis regulators SHORT INTERNODE/ STYLISH (SHI/STY) during Physcomitrella patens reproductive development, we have described male (antheridial) and female (archegonial) development in detail, including temporal and positional information of organ initiation. This has allowed us to define discrete stages of organ morphogenesis and to show that reproductive organ development in P. patens is highly organized and that organ phyllotaxis differs between vegetative and reproductive development. Using the PpSHI1 and PpSHI2 reporter and knockout lines, the auxin reporters GmGH3pro:GUS and PpPINApro:GFP-GUS, and the auxin-conjugating transgene PpSHI2pro:IAAL, we could show that the PpSHI genes, and by inference also auxin, play important roles for reproductive organ development in moss. The PpSHI genes are required for the apical opening of the reproductive organs, the final differentiation of the egg cell, and the progression of canal cells into a cell death program. The apical cells of the archegonium, the canal cells, and the egg cell are also sites of auxin responsiveness and are affected by reduced levels of active auxin, suggesting that auxin mediates PpSHI function in the reproductive organs.

High-precision Taylor-Couette experiment to study subcritical transitions and the role of boundary conditions and size effects - Avila, Kerstin; Hof, Björn (Review of Scientific Instruments)
A novel Taylor-Couette system has been constructed for investigations of transitional as well as high Reynolds number turbulent flows in very large aspect ratios. The flexibility of the setup enables studies of a variety of problems regarding hydrodynamic instabilities and turbulence in rotating flows. The inner and outer cylinders and the top and bottom endplates can be rotated independently with rotation rates of up to 30 Hz, thereby covering five orders of magnitude in Reynolds numbers (Re = 101-106). The radius ratio can be easily changed, the highest realized one is η = 0.98 corresponding to an aspect ratio of 260 gap width in the vertical and 300 in the azimuthal direction. For η < 0.98 the aspect ratio can be dynamically changed during measurements and complete transparency in the radial direction over the full length of the cylinders is provided by the usage of a precision glass inner cylinder. The temperatures of both cylinders are controlled independently. Overall this apparatus combines an unmatched variety in geometry, rotation rates, and temperatures, which is provided by a sophisticated high-precision bearing system. Possible applications are accurate studies of the onset of turbulence and spatio-temporal intermittent flow patterns in very large domains, transport processes of turbulence at high Re, the stability of Keplerian flows for different boundary conditions, and studies of baroclinic instabilities.

Environmental dependence of genetic constraint - De Vos, Marjon; Poelwijk, Frank; Battich, Nico; Ndika, Joseph; Tans, Sander (PLoS Genetics)
The epistatic interactions that underlie evolutionary constraint have mainly been studied for constant external conditions. However, environmental changes may modulate epistasis and hence affect genetic constraints. Here we investigate genetic constraints in the adaptive evolution of a novel regulatory function in variable environments, using the lac repressor, LacI, as a model system. We have systematically reconstructed mutational trajectories from wild type LacI to three different variants that each exhibit an inverse response to the inducing ligand IPTG, and analyzed the higher-order interactions between genetic and environmental changes. We find epistasis to depend strongly on the environment. As a result, mutational steps essential to inversion but inaccessible by positive selection in one environment, become accessible in another. We present a graphical method to analyze the observed complex higher-order interactions between multiple mutations and environmental change, and show how the interactions can be explained by a combination of mutational effects on allostery and thermodynamic stability. This dependency of genetic constraint on the environment should fundamentally affect evolutionary dynamics and affects the interpretation of phylogenetic data.

The complexity of coverage - Chatterjee, Krishnendu; Alfaro, Luca; Majumdar, Ritankar (International Journal of Foundations of Computer Science)
We study the problem of generating a test sequence that achieves maximal coverage for a reactive system under test. We formulate the problem as a repeated game between the tester and the system, where the system state space is partitioned according to some coverage criterion and the objective of the tester is to maximize the set of partitions (or coverage goals) visited during the game. We show the complexity of the maximal coverage problem for non-deterministic systems is PSPACE-complete, but is NP-complete for deterministic systems. For the special case of non-deterministic systems with a re-initializing "reset" action, which represent running a new test input on a re-initialized system, we show that the complexity is coNP-complete. Our proof technique for reset games uses randomized testing strategies that circumvent the exponentially large memory requirement of deterministic testing strategies. We also discuss the memory requirement for deterministic strategies and extensions of our results to other models, such as pushdown systems and timed systems.

Nature of laminar-turbulence intermittency in shear flows - Avila, Marc; Hof, Björn (Physical Review E)
In pipe, channel, and boundary layer flows turbulence first occurs intermittently in space and time: at moderate Reynolds numbers domains of disordered turbulent motion are separated by quiescent laminar regions. Based on direct numerical simulations of pipe flow we argue here that the spatial intermittency has its origin in a nearest neighbor interaction between turbulent regions. We further show that in this regime turbulent flows are intrinsically intermittent with a well-defined equilibrium turbulent fraction but without ever assuming a steady pattern. This transition scenario is analogous to that found in simple models such as coupled map lattices. The scaling observed implies that laminar intermissions of the turbulent flow will persist to arbitrarily large Reynolds numbers.

Elasto-inertial turbulence - Samanta, Devranjan; Dubief, Yves; Holzner, Markus; Schäfer, Christof; Morozov, Alexander; Wagner, Christian; Hof, Björn (PNAS)
Turbulence is ubiquitous in nature, yet even for the case of ordinary Newtonian fluids like water, our understanding of this phenomenon is limited. Many liquids of practical importance are more complicated (e.g., blood, polymer melts, paints), however; they exhibit elastic as well as viscous characteristics, and the relation between stress and strain is nonlinear. We demonstrate here for a model system of such complex fluids that at high shear rates, turbulence is not simply modified as previously believed but is suppressed and replaced by a different type of disordered motion, elasto-inertial turbulence. Elasto-inertial turbulence is found to occur at much lower Reynolds numbers than Newtonian turbulence, and the dynamical properties differ significantly. The friction scaling observed coincides with the so-called "maximum drag reduction" asymptote, which is exhibited by a wide range of viscoelastic fluids.

Homological reconstruction and simplification in R3 - Attali, Dominique; Bauer, Ulrich; Devillers, Olivier; Glisse, Marc; Lieutier, André (Proceedings of the 29th annual symposium on Computational Geometry)
We consider the problem of deciding whether the persistent homology group of a simplicial pair (K, L) can be realized as the homology H* (X) of some complex X with L ⊂ X ⊂ K. We show that this problem is NP-complete even if K is embedded in ℝ3. As a consequence, we show that it is NP-hard to simplify level and sublevel sets of scalar functions on S3 within a given tolerance constraint. This problem has relevance to the visualization of medical images by isosurfaces. We also show an implication to the theory of well groups of scalar functions: not every well group can be realized by some level set, and deciding whether a well group can be realized is NP-hard.

Density games - Novak, Sebastian; Chatterjee, Krishnendu; Nowak, Martin (Journal of Theoretical Biology)
The basic idea of evolutionary game theory is that payoff determines reproductive rate. Successful individuals have a higher payoff and produce more offspring. But in evolutionary and ecological situations there is not only reproductive rate but also carrying capacity. Individuals may differ in their exposure to density limiting effects. Here we explore an alternative approach to evolutionary game theory by assuming that the payoff from the game determines the carrying capacity of individual phenotypes. Successful strategies are less affected by density limitation (crowding) and reach higher equilibrium abundance. We demonstrate similarities and differences between our framework and the standard replicator equation. Our equation is defined on the positive orthant, instead of the simplex, but has the same equilibrium points as the replicator equation. Linear stability analysis produces the classical conditions for asymptotic stability of pure strategies, but the stability properties of internal equilibria can differ in the two frameworks. For example, in a two-strategy game with an internal equilibrium that is always stable under the replicator equation, the corresponding equilibrium can be unstable in the new framework resulting in a limit cycle.

Quantitative timed simulation functions and refinement metrics for real-time systems - Chatterjee, Krishnendu; Prabhu, Vinayak (Proceedings of the 16th International Conference on Hybrid Systems: Computation and Control)
We introduce quantatitive timed refinement metrics and quantitative timed simulation functions, incorporating zenoness checks, for timed systems. These functions assign positive real numbers between zero and infinity which quantify the timing mismatches between two timed systems, amongst non-zeno runs. We quantify timing mismatches in three ways: (1) the maximum timing mismatch that can arise, (2) the "steady-state" maximum timing mismatches, where initial transient timing mismatches are ignored; and (3) the (long-run) average timing mismatches amongst two systems. These three kinds of mismatches constitute three important types of timing differences. Our event times are the global times, measured from the start of the system execution, not just the time durations of individual steps. We present algorithms over timed automata for computing the three quantitative simulation functions to within any desired degree of accuracy. In order to compute the values of the quantitative simulation functions, we use a game theoretic formulation. We introduce two new kinds of objectives for two player games on finite state game graphs: (1) eventual debit-sum level objectives, and (2) average debit-sum level objectives. We present algorithms for computing the optimal values for these objectives for player 1, and then use these algorithms to compute the values of the quantitative timed simulation functions.

Learning quadratic receptive fields from neural responses to natural stimuli - Rajan, Kanaka; Marre, Olivier; Tkacik, Gasper (Neural Computation)
Models of neural responses to stimuli with complex spatiotemporal correlation structure often assume that neurons are selective for only a small number of linear projections of a potentially high-dimensional input. In this review, we explore recent modeling approaches where the neural response depends on the quadratic form of the input rather than on its linear projection, that is, the neuron is sensitive to the local covariance structure of the signal preceding the spike. To infer this quadratic dependence in the presence of arbitrary (e.g., naturalistic) stimulus distribution, we review several inference methods, focusing in particular on two information theory–based approaches (maximization of stimulus energy and of noise entropy) and two likelihood-based approaches (Bayesian spike-triggered covariance and extensions of generalized linear models). We analyze the formal relationship between the likelihood-based and information-based approaches to demonstrate how they lead to consistent inference. We demonstrate the practical feasibility of these procedures by using model neurons responding to a flickering variance stimulus.

Mutations in SCO2 are associated with autosomal-dominant high-grade myopia - Tran Viet, Khanh; Powell, Caldwell; Barathi, Veluchamy; Klemm, Thomas; Maurer Stroh, Sebastian; Limviphuvadh, Vachiranee; Soler, Vincent; Ho, Candice; Yanovitch, Tammy; Schneider, Georg; Li, Yi; Nading, Erica; et al. (American Journal of Human Genetics)
Myopia, or near-sightedness, is an ocular refractive error of unfocused image quality in front of the retinal plane. Individuals with high-grade myopia (dioptric power greater than -6.00) are predisposed to ocular morbidities such as glaucoma, retinal detachment, and myopic maculopathy. Nonsyndromic, high-grade myopia is highly heritable, and to date multiple gene loci have been reported. We performed exome sequencing in 4 individuals from an 11-member family of European descent from the United States. Affected individuals had a mean dioptric spherical equivalent of -22.00 sphere. A premature stop codon mutation c.157C>T (p.Gln53*) cosegregating with disease was discovered within SCO2 that maps to chromosome 22q13.33. Subsequent analyses identified three additional mutations in three highly myopic unrelated individuals (c.341G>A, c.418G>A, and c.776C>T). To determine differential gene expression in a developmental mouse model, we induced myopia by applying a -15.00D lens over one eye. Messenger RNA levels of SCO2 were significantly downregulated in myopic mouse retinae. Immunohistochemistry in mouse eyes confirmed SCO2 protein localization in retina, retinal pigment epithelium, and sclera. SCO2 encodes for a copper homeostasis protein influential in mitochondrial cytochrome c oxidase activity. Copper deficiencies have been linked with photoreceptor loss and myopia with increased scleral wall elasticity. Retinal thinning has been reported with an SC02 variant. Human mutation identification with support from an induced myopic animal provides biological insights of myopic development.

3D phenotyping and quantitative trait locus mapping identify core regions of the rice genome controlling root architecture - Topp, Christopher; Iyer Pascuzzi, Anjali; Anderson, Jill; Lee, Cheng; Zurek, Paul; Symonova, Olga; Zheng, Ying; Bucksch, Alexander; Mileyko, Yuriy; Galkovskyi, Taras; Moore, Brad; Harer, John; et al. (PNAS)
Identification of genes that control root system architecture in crop plants requires innovations that enable high-throughput and accurate measurements of root system architecture through time. We demonstrate the ability of a semiautomated 3D in vivo imaging and digital phenotyping pipeline to interrogate the quantitative genetic basis of root system growth in a rice biparental mapping population, Bala x Azucena. We phenotyped >1,400 3D root models and >57,000 2D images for a suite of 25 traits that quantified the distribution, shape, extent of exploration, and the intrinsic size of root networks at days 12, 14, and 16 of growth in a gellan gum medium. From these data we identified 89 quantitative trait loci, some of which correspond to those found previously in soil-grown plants, and provide evidence for genetic tradeoffs in root growth allocations, such as between the extent and thoroughness of exploration. We also developed a multivariate method for generating and mapping central root architecture phenotypes and used it to identify five major quantitative trait loci (r2 = 24-37%), two of which were not identified by our univariate analysis. Our imaging and analytical platform provides a means to identify genes with high potential for improving root traits and agronomic qualities of crops.

A major facilitator superfamily transporter plays a dual role in polar auxin transport and drought stress tolerance in Arabidopsis - Remy, Estelle; Cabrito, Tânia; Baster, Pawel; Batista, Rita; Teixeira, Miguel; Friml, Jirí; Sá Correia, Isabel; Duque, Paula (Plant Cell)
Many key aspects of plant development are regulated by the polarized transport of the phytohormone auxin. Cellular auxin efflux, the rate-limiting step in this process, has been shown to rely on the coordinated action of PIN-formed (PIN) and B-type ATP binding cassette (ABCB) carriers. Here, we report that polar auxin transport in the Arabidopsis thaliana root also requires the action of a Major Facilitator Superfamily (MFS) transporter, Zinc-Induced Facilitator-Like 1 (ZIFL1). Sequencing, promoter-reporter, and fluorescent protein fusion experiments indicate that the full-length ZIFL1.1 protein and a truncated splice isoform, ZIFL1.3, localize to the tonoplast of root cells and the plasma membrane of leaf stomatal guard cells, respectively. Using reverse genetics, we show that the ZIFL1.1 transporter regulates various root auxin-related processes, while the ZIFL1.3 isoform mediates drought tolerance by regulating stomatal closure. Auxin transport and immunolocalization assays demonstrate that ZIFL1.1 indirectly modulates cellular auxin efflux during shootward auxin transport at the root tip, likely by regulating plasma membrane PIN2 abundance. Finally, heterologous expression in yeast revealed that ZIFL1.1 and ZIFL1.3 share H+-coupled K+ transport activity. Thus, by determining the subcellular and tissue distribution of two isoforms, alternative splicing dictates a dual function for the ZIFL1 transporter. We propose that this MFS carrier regulates stomatal movements and polar auxin transport by modulating potassium and proton fluxes in Arabidopsis cells.

Salicylic acid interferes with clathrin-mediated endocytic protein trafficking - Du, Yunlong; Tejos, Ricardo; Beck, Martina; Himschoot, Ellie; Li, Hongjiang; Robatzek, Silke; Vanneste, Steffen; Friml, Jirí (PNAS)
Removal of cargos from the cell surface via endocytosis is an efficient mechanism to regulate activities of plasma membrane (PM)-resident proteins, such as receptors or transporters. Salicylic acid (SA) is an important plant hormone that is traditionally associated with pathogen defense. Here, we describe an unanticipated effect of SA on subcellular endocytic cycling of proteins. Both exogenous treatments and endogenously enhanced SA levels repressed endocytosis of different PM proteins. The SA effect on endocytosis did not involve transcription or known components of the SA signaling pathway for transcriptional regulation. SA likely targets an endocytic mechanism that involves the coat protein clathrin, because SA interfered with the clathrin incidence at the PM and clathrin-deficient mutants were less sensitive to the impact of SA on the auxin distribution and root bending during the gravitropic response. By contrast, SA did not affect the ligand-induced endocytosis of the FLAGELLIN SENSING2 (FLS2) receptor during pathogen responses. Our data suggest that the established SA impact on transcription in plant immunity and the nontranscriptional effect of SA on clathrin-mediated endocytosis are independent mechanisms by which SA regulates distinct aspects of plant physiology.

Post-fire recovery of revegetated woodland communities in south-eastern Australia - Pickup, Melinda; Wilson, Susie; Freudenberger, David; Nicholls, Nick; Gould, Lori; Hnatiuk, Sarah; Delandre, Jeni (Austral Ecology)
The primary goal of restoration is to create self-sustaining ecological communities that are resilient to periodic disturbance. Currently, little is known about how restored communities respond to disturbance events such as fire and how this response compares to remnant vegetation. Following the 2003 fires in south-eastern Australia we examined the post-fire response of revegetation plantings and compared this to remnant vegetation. Ten burnt and 10 unburnt (control) sites were assessed for each of three types of vegetation (direct seeding revegetation, revegetation using nursery seedlings (tubestock) and remnant woodland). Sixty sampling sites were surveyed 6months after fire to quantify the initial survival of mid- and overstorey plant species in each type of vegetation. Three and 5years after fire all sites were resurveyed to assess vegetation structure, species diversity and vigour, as well as indicators of soil function. Overall, revegetation showed high (>60%) post-fire survival, but this varied among species depending on regeneration strategy (obligate seeder or resprouter). The native ground cover, mid- and overstorey in both types of plantings showed rapid recovery of vegetation structure and cover within 3years of fire. This recovery was similar to the burnt remnant woodlands. Non-native (exotic) ground cover initially increased after fire, but was no different in burnt and unburnt sites 5years after fire. Fire had no effect on species richness, but burnt direct seeding sites had reduced species diversity (Simpson's Diversity Index) while diversity was higher in burnt remnant woodlands. Indices of soil function in all types of vegetation had recovered to levels found in unburnt sites 5years after fire. These results indicate that even young revegetation (stands <10years old) showed substantial recovery from disturbance by fire. This suggests that revegetation can provide an important basis for restoring woodland communities in the fire-prone Australian environment.

Synthesis of memory-efficient, clock-memory free, and non-Zeno safety controllers for timed systems - Chatterjee, Krishnendu; Prabhu, Vinayak (Information and Computation)
We study synthesis of controllers for real-time systems, where the objective is to stay in a given safe set. The problem is solved by obtaining winning strategies in the setting of concurrent two player timed automaton games with safety objectives. To prevent a player from winning by blocking time, we restrict each player to strategies that ensure that the player cannot be responsible for causing a Zeno run. We construct winning strategies for the controller which require access only to (1) the system clocks (thus, controllers which require their own internal infinitely precise clocks are not necessary), and (2) a logarithmic (in the number of clocks) number of memory bits (i.e. a linear number of memory states). Precisely, we show that for safety objectives, a memory of size (3 + lg (| C | + 1)) bits suffices for winning controller strategies, where C is the set of clocks of the timed automaton game, significantly improving the previous known exponential memory states bound. We also settle the open question of whether winning region-based strategies require memory for safety objectives by showing with an example the necessity of memory for such strategies to win for safety objectives. Finally, we show that the decision problem of determining if there exists a receptive player-1 winning strategy for safety objectives is EXPTIME-complete over timed automaton games.

Cell polarity and patterning by PIN trafficking through early endosomal compartments in arabidopsis thaliana - Tanaka, Hirokazu; Kitakura, Saeko; Rakusová, Hana; Uemura, Tomohiro; Feraru, Mugurel; De Rycke, Riet; Robert, Stéphanie; Kakimoto, Tatsuo; Friml, Jirí (PLoS Genetics)
PIN-FORMED (PIN) proteins localize asymmetrically at the plasma membrane and mediate intercellular polar transport of the plant hormone auxin that is crucial for a multitude of developmental processes in plants. PIN localization is under extensive control by environmental or developmental cues, but mechanisms regulating PIN localization are not fully understood. Here we show that early endosomal components ARF GEF BEN1 and newly identified Sec1/Munc18 family protein BEN2 are involved in distinct steps of early endosomal trafficking. BEN1 and BEN2 are collectively required for polar PIN localization, for their dynamic repolarization, and consequently for auxin activity gradient formation and auxin-related developmental processes including embryonic patterning, organogenesis, and vasculature venation patterning. These results show that early endosomal trafficking is crucial for cell polarity and auxin-dependent regulation of plant architecture.

The complexity of conservative valued CSPs - Kolmogorov, Vladimir; Živný, Stanislav (Journal of the ACM)
We study the complexity of valued constraint satisfaction problems (VCSPs) parametrized by a constraint language, a fixed set of cost functions over a finite domain. An instance of the problem is specified by a sum of cost functions from the language and the goal is to minimize the sum. Under the unique games conjecture, the approximability of finite-valued VCSPs is well understood, see Raghavendra [2008]. However, there is no characterization of finite-valued VCSPs, let alone general-valued VCSPs, that can be solved exactly in polynomial time, thus giving insights from a combinatorial optimization perspective. We consider the case of languages containing all possible unary cost functions. In the case of languages consisting of only {0, ∞}-valued cost functions (i.e., relations), such languages have been called conservative and studied by Bulatov [2003, 2011] and recently by Barto [2011]. Since we study valued languages, we call a language conservative if it contains all finite-valued unary cost functions. The computational complexity of conservative valued languages has been studied by Cohen et al. [2006] for languages over Boolean domains, by Deineko et al. [2008] for {0, 1}-valued languages (a.k.a Max-CSP), and by Takhanov [2010a] for {0, ∞}-valued languages containing all finite-valued unary cost functions (a.k.a. Min-Cost-Hom). We prove a Schaefer-like dichotomy theorem for conservative valued languages: if all cost functions in the language satisfy a certain condition (specified by a complementary combination of STP and MJN multimor-phisms), then any instance can be solved in polynomial time (via a new algorithm developed in this article), otherwise the language is NP-hard. This is the first complete complexity classification of general-valued constraint languages over non-Boolean domains. It is a common phenomenon that complexity classifications of problems over non-Boolean domains are significantly harder than the Boolean cases. The polynomial-time algorithm we present for the tractable cases is a generalization of the submodular minimization problem and a result of Cohen et al. [2008]. Our results generalize previous results by Takhanov [2010a] and (a subset of results) by Cohen et al. [2006] and Deineko et al. [2008]. Moreover, our results do not rely on any computer-assisted search as in Deineko et al. [2008], and provide a powerful tool for proving hardness of finite-valued and general-valued languages.

Scale invariance at the onset of turbulence in couette flow - Shi, Liang; Avila, Marc; Hof, Björn (Physical Review Letters)
Laminar-turbulent intermittency is intrinsic to the transitional regime of a wide range of fluid flows including pipe, channel, boundary layer, and Couette flow. In the latter turbulent spots can grow and form continuous stripes, yet in the stripe-normal direction they remain interspersed by laminar fluid. We carry out direct numerical simulations in a long narrow domain and observe that individual turbulent stripes are transient. In agreement with recent observations in pipe flow, we find that turbulence becomes sustained at a distinct critical point once the spatial proliferation outweighs the inherent decaying process. By resolving the asymptotic size distributions close to criticality we can for the first time demonstrate scale invariance at the onset of turbulence.

Streamwise-localized solutions at the onset of turbulence in pipe flow - Avila, Marc; Mellibovsky, Fernando; Roland, Nicolas; Hof, Björn (Physical Review Letters)
Although the equations governing fluid flow are well known, there are no analytical expressions that describe the complexity of turbulent motion. A recent proposition is that in analogy to low dimensional chaotic systems, turbulence is organized around unstable solutions of the governing equations which provide the building blocks of the disordered dynamics. We report the discovery of periodic solutions which just like intermittent turbulence are spatially localized and show that turbulent transients arise from one such solution branch.

Forces in tissue morphogenesis and patterning - Heisenberg, Carl-Philipp J; Bellaïche, Yohanns (Cell)
During development, mechanical forces cause changes in size, shape, number, position, and gene expression of cells. They are therefore integral to any morphogenetic processes. Force generation by actin-myosin networks and force transmission through adhesive complexes are two self-organizing phenomena driving tissue morphogenesis. Coordination and integration of forces by long-range force transmission and mechanosensing of cells within tissues produce large-scale tissue shape changes. Extrinsic mechanical forces also control tissue patterning by modulating cell fate specification and differentiation. Thus, the interplay between tissue mechanics and biochemical signaling orchestrates tissue morphogenesis and patterning in development.

A conduit to amplify innate immunity - Moussion, Christine; Sixt, Michael K (Immunity)

Inference in two dimensions: Allele frequencies versus lengths of shared sequence blocks - Barton, Nicholas H; Etheridge, Alison; Kelleher, Jerome; Véber, Amandine (Theoretical Population Biology)
We outline two approaches to inference of neighbourhood size, N, and dispersal rate, σ2, based on either allele frequencies or on the lengths of sequence blocks that are shared between genomes. Over intermediate timescales (10-100 generations, say), populations that live in two dimensions approach a quasi-equilibrium that is independent of both their local structure and their deeper history. Over such scales, the standardised covariance of allele frequencies (i.e. pairwise FS T) falls with the logarithm of distance, and depends only on neighbourhood size, N, and a 'local scale', κ; the rate of gene flow, σ2, cannot be inferred. We show how spatial correlations can be accounted for, assuming a Gaussian distribution of allele frequencies, giving maximum likelihood estimates of N and κ. Alternatively, inferences can be based on the distribution of the lengths of sequence that are identical between blocks of genomes: long blocks (>0.1 cM, say) tell us about intermediate timescales, over which we assume a quasi-equilibrium. For large neighbourhood size, the distribution of long blocks is given directly by the classical Wright-Malécot formula; this relationship can be used to infer both N and σ2. With small neighbourhood size, there is an appreciable chance that recombinant lineages will coalesce back before escaping into the distant past. For this case, we show that if genomes are sampled from some distance apart, then the distribution of lengths of blocks that are identical in state is geometric, with a mean that depends on N and σ2.

Dyrk1A is dynamically expressed on subsets of motor neurons and in the neuromuscular junction: Possible role in Down syndrome - Arquè Fuste, Gloria; Casanovas, Anna; Dierssen, Mara (PLoS One)
Individuals with Down syndrome (DS) present important motor deficits that derive from altered motor development of infants and young children. DYRK1A, a candidate gene for DS abnormalities has been implicated in motor function due to its expression in motor nuclei in the adult brain, and its overexpression in DS mouse models leads to hyperactivity and altered motor learning. However, its precise role in the adult motor system, or its possible involvement in postnatal locomotor development has not yet been clarified. During the postnatal period we observed time-specific expression of Dyrk1A in discrete subsets of brainstem nuclei and spinal cord motor neurons. Interestingly, we describe for the first time the presence of Dyrk1A in the presynaptic terminal of the neuromuscular junctions and its axonal transport from the facial nucleus, suggesting a function for Dyrk1A in these structures. Relevant to DS, Dyrk1A overexpression in transgenic mice (TgDyrk1A) produces motor developmental alterations possibly contributing to DS motor phenotypes and modifies the numbers of motor cholinergic neurons, suggesting that the kinase may have a role in the development of the brainstem and spinal cord motor system.

Interstitial dendritic cell guidance by haptotactic chemokine gradients - Weber, Michele; Hauschild, Robert; Schwarz, Jan; Moussion, Christine; De Vries, Ingrid; Legler, Daniel; Luther, Sanjiv; Bollenbach, Mark Tobias; Sixt, Michael K (Science)
Directional guidance of cells via gradients of chemokines is considered crucial for embryonic development, cancer dissemination, and immune responses. Nevertheless, the concept still lacks direct experimental confirmation in vivo. Here, we identify endogenous gradients of the chemokine CCL21 within mouse skin and show that they guide dendritic cells toward lymphatic vessels. Quantitative imaging reveals depots of CCL21 within lymphatic endothelial cells and steeply decaying gradients within the perilymphatic interstitium. These gradients match the migratory patterns of the dendritic cells, which directionally approach vessels from a distance of up to 90-micrometers. Interstitial CCL21 is immobilized to heparan sulfates, and its experimental delocalization or swamping the endogenous gradients abolishes directed migration. These findings functionally establish the concept of haptotaxis, directed migration along immobilized gradients, in tissues.

The local semicircle law for a general class of random matrices - Erdös, László; Knowles, Antti; Yau, Horng; Yin, Jun (Electronic Journal of Probability)
We consider a general class of N × N random matrices whose entries hij are independent up to a symmetry constraint, but not necessarily identically distributed. Our main result is a local semicircle law which improves previous results [17] both in the bulk and at the edge. The error bounds are given in terms of the basic small parameter of the model, maxi,j E|hij|2. As a consequence, we prove the universality of the local n-point correlation functions in the bulk spectrum for a class of matrices whose entries do not have comparable variances, including random band matrices with band width W ≫N1-εn with some εn > 0 and with a negligible mean-field component. In addition, we provide a coherent and pedagogical proof of the local semicircle law, streamlining and strengthening previous arguments from [17, 19, 6].

Root ultraviolet b-sensitive1/weak auxin response3 is essential for polar auxin transport in arabidopsis - Yu, Hong; Karampelias, Michael; Robert, Stéphanie; Peer, Wendy; Swarup, Ranjan; Ye, Songqing; Ge, Lei; Cohen, Jerry; Murphy, Angus; Friml, Jirí; Estelle, Mark (Plant Physiology)
The phytohormone auxin regulates virtually every aspect of plant development. To identify new genes involved in auxin activity, a genetic screen was performed for Arabidopsis (Arabidopsis thaliana) mutants with altered expression of the auxin-responsive reporter DR5rev:GFP. One of the mutants recovered in the screen, designated as weak auxin response3 (wxr3), exhibits much lower DR5rev:GFP expression when treated with the synthetic auxin 2,4-dichlorophenoxyacetic acid and displays severe defects in root development. The wxr3 mutant decreases polar auxin transport and results in a disruption of the asymmetric auxin distribution. The levels of the auxin transporters AUXIN1 and PIN-FORMED are dramatically reduced in the wxr3 root tip. Molecular analyses demonstrate that WXR3 is ROOT ULTRAVIOLET B-SENSITIVE1 (RUS1), a member of the conserved Domain of Unknown Function647 protein family found in diverse eukaryotic organisms. Our data suggest that RUS1/WXR3 plays an essential role in the regulation of polar auxin transport by maintaining the proper level of auxin transporters on the plasma membrane.

Assume-guarantee synthesis for digital contract signing - Chatterjee, Krishnendu; Raman, Vishwanath (Formal Aspects of Computing)
We study the automatic synthesis of fair non-repudiation protocols, a class of fair exchange protocols, used for digital contract signing. First, we show how to specify the objectives of the participating agents and the trusted third party as path formulas in linear temporal logic and prove that the satisfaction of these objectives imply fairness; a property required of fair exchange protocols. We then show that weak (co-operative) co-synthesis and classical (strictly competitive) co-synthesis fail, whereas assume-guarantee synthesis (AGS) succeeds. We demonstrate the success of AGS as follows: (a) any solution of AGS is attack-free; no subset of participants can violate the objectives of the other participants; (b) the Asokan-Shoup-Waidner certified mail protocol that has known vulnerabilities is not a solution of AGS; (c) the Kremer-Markowitch non-repudiation protocol is a solution of AGS; and (d) AGS presents a new and symmetric fair non-repudiation protocol that is attack-free. To our knowledge this is the first application of synthesis to fair non-repudiation protocols, and our results show how synthesis can both automatically discover vulnerabilities in protocols and generate correct protocols. The solution to AGS can be computed efficiently as the secure equilibrium solution of three-player graph games.

Distinct roles of medial and lateral entorhinal cortex in spatial cognition - Van Cauter, Tiffany; Camon, Jeremy; Alvernhe, Alice; Elduayen, Coralie; Sargolini, Francesca; Save, Étienne (Cerebral Cortex)
It is known that the entorhinal cortex plays a crucial role in spatial cognition in rodents. Neuroanatomical and electrophysiological data suggest that there is a functional distinction between 2 subregions within the entorhinal cortex, the medial entorhinal cortex (MEC), and the lateral entorhinal cortex (LEC). Rats with MEC or LEC lesions were trained in 2 navigation tasks requiring allothetic (water maze task) or idiothetic (path integration) information processing and 2-object exploration tasks allowing testing of spatial and nonspatial processing of intramaze objects. MEC lesions mildly affected place navigation in the water maze and produced a path integration deficit. They also altered the processing of spatial information in both exploration tasks while sparing the processing of nonspatial information. LEC lesions did not affect navigation abilities in both the water maze and the path integration tasks. They altered spatial and nonspatial processing in the object exploration task but not in the one-trial recognition task. Overall, these results indicate that the MEC is important for spatial processing and path integration. The LEC has some influence on both spatial and nonspatial processes, suggesting that the 2 kinds of information interact at the level of the EC.

Holding on and letting go: Cadherin turnover in cell intercalation - Morita, Hitoshi; Heisenberg, Carl-Philipp J (Developmental Cell)
In zebrafish early development, blastoderm cells undergo extensive radial intercalations, triggering the spreading of the blastoderm over the yolk cell and thereby initiating embryonic body axis formation. Now reporting in Developmental Cell, Song et al. (2013) demonstrate a critical function for EGF-dependent E-cadherin endocytosis in promoting blastoderm cell intercalations.

An auxin transport mechanism restricts positive orthogravitropism in lateral roots - Rosquete, Michel; Von Wangenheim, Daniel; Marhavy, Peter; Barbez, Elke; Stelzer, Ernst; Benková, Eva; Maizel, Alexis; Kleine Vehn, Jürgen (Current Biology)
As soon as a seed germinates, plant growth relates to gravity to ensure that the root penetrates the soil and the shoot expands aerially. Whereas mechanisms of positive and negative orthogravitropism of primary roots and shoots are relatively well understood [1-3], lateral organs often show more complex growth behavior [4]. Lateral roots (LRs) seemingly suppress positive gravitropic growth and show a defined gravitropic set-point angle (GSA) that allows radial expansion of the root system (plagiotropism) [3, 4]. Despite its eminent importance for root architecture, it so far remains completely unknown how lateral organs partially suppress positive orthogravitropism. Here we show that the phytohormone auxin steers GSA formation and limits positive orthogravitropism in LR. Low and high auxin levels/signaling lead to radial or axial root systems, respectively. At a cellular level, it is the auxin transport-dependent regulation of asymmetric growth in the elongation zone that determines GSA. Our data suggest that strong repression of PIN4/PIN7 and transient PIN3 expression limit auxin redistribution in young LR columella cells. We conclude that PIN activity, by temporally limiting the asymmetric auxin fluxes in the tip of LRs, induces transient, differential growth responses in the elongation zone and, consequently, controls root architecture.

Stable length estimates of tube-like shapes - Edelsbrunner, Herbert; Pausinger, Florian (17th IAPR International Conference on Discrete Geometry for Computer Imagery)
Mathematical objects can be measured unambiguously, but not so objects from our physical world. Even the total length of tubelike shapes has its difficulties. We introduce a combination of geometric, probabilistic, and topological methods to design a stable length estimate for tube-like shapes; that is: one that is insensitive to small shape changes.

Developmental refinement of vesicle cycling at Schaffer collateral synapses - Rose, Tobias; Schönenberger, Philipp; Jezek, Karel; Oertner, Thomas (Neuron)
At synapses formed between dissociated neurons, about half of all synaptic vesicles are refractory to evoked release, forming the so-called "resting pool." Here, we use optical measurements of vesicular pH to study developmental changes in pool partitioning and vesicle cycling in cultured hippocampal slices. Two-photon imaging of a genetically encoded two-color release sensor (ratio-sypHy) allowed us to perform calibrated measurements at individual Schaffer collateral boutons. Mature boutons released a large fraction of their vesicles during simulated place field activity, and vesicle retrieval rates were 7-fold higher compared to immature boutons. Saturating stimulation mobilized essentially all vesicles at mature synapses. Resting pool formation and a concomitant reduction in evoked release was induced by chronic depolarization but not by acute inhibition of the protein phosphatase calcineurin. We conclude that synapses in CA1 undergo a prominent refinement of vesicle use during early postnatal development that is not recapitulated in dissociated neuronal culture.